Method for producing polyurethane composite material, polyurethane composite material and dental cutting material

By using polyurethane composite materials in dental cutting materials, including addition reaction, radical polymerizable raw material composition preparation and radical polymerization process, the shortcomings of existing materials in terms of strength and water resistance are solved. Material properties with high strength, water resistance and uniformity are achieved.

CN114846039BActive Publication Date: 2025-02-25TOKUYAMA DENTAL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180007558.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-28
Filing Date
2021-01-22
Publication Date
2025-02-25
Estimated Expiration
2041-01-22

AI Technical Summary

Technical Problem

The existing dental cutting materials have shortcomings in strength and water resistance, especially in water environments, where the material's performance is poor.

Method used

A method for producing a polyurethane composite material is adopted, which includes a polymerization reaction step, a radical polymerizable raw material composition preparation step and a radical polymerization step, through which polyurethanes with high strength, water resistance and uniformity are formed. Composite material.

Benefits of technology

It achieves high strength, water resistance and uniformity of the material, ensures stable performance in a water environment, and is suitable for materials for dental cutting processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005035253570000011
    Figure FDA0005035253570000011
  • Figure FDA0005035253570000031
    Figure FDA0005035253570000031
  • Figure FDA0005035253570000041
    Figure FDA0005035253570000041
Patent Text Reader

Abstract

The present invention manufactures a hardened body having excellent strength, water resistance and uniformity. The method for manufacturing a polyurethane composite material of the present invention comprises: an addition polymerization step, in which a polyurethane component (A) having a number average molecular weight of 1500 to 5000 is formed by performing an addition polymerization in a first raw material composition comprising a free radical polymerizable monomer (B) which does not undergo an addition polymerization reaction with a free radical polymerizable diol compound (a1) and a diisocyanate compound (a2); a second raw material composition preparation step, in which a second raw material composition comprising a component (A), a component (B), a free radical polymerization initiator and a filler is prepared; and a free radical polymerization step, in which, after completing the addition polymerization step and the second raw material composition preparation step, the second raw material composition is used for free radical polymerization, wherein the ratio (R) represented by the following formula (1) is 20 wt % to 80 wt %, where R=100×B / [a1+a2+A+B], wherein (a1), (a2), (A) and (B) are the contents (parts by mass) of the components (a1), (a2), (A) and (B) in the second raw material composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for producing a polyurethane composite material, a polyurethane composite material and a material for dental cutting. Background Art

[0002] In dental treatment, as a method for manufacturing dental prostheses such as inlays, onlays, crowns, bridges, and implant superstructures, there is cutting processing using a dental CAD / CAM system. A dental CAD / CAM system refers to a system that designs dental prostheses based on three-dimensional coordinate data using a computer and manufactures crown restorations using a cutting machine or the like. As cutting materials, various materials such as glass ceramics, zirconium oxide, titanium, and resins are used. As dental cutting resin materials, a curable composition containing inorganic fillers such as silica, polymerizable monomers such as methacrylate, and polymerization initiators is used, and the composition is hardened into a block or disc-shaped hardened material. As for cutting materials, by effectively utilizing a computer system, compared with existing methods for manufacturing dental prostheses, it has attracted great attention from the perspectives of fewer steps, higher workability, and aesthetics and strength of the hardened body.

[0003] Such cutting materials are mainly used for tooth crowns, and when used as molar crowns or bridges, higher strength is required. However, existing cutting materials are mainly (meth) acrylic resins, which have a problem of limited strength.

[0004] In contrast, it is known that polyurethane resins generally have high strength, and therefore, research has been conducted to use them as dental materials. For example, in Patent Document 1, polyurethane resins for use as dental materials and methods for their manufacture are proposed. The manufacturing method includes a two-stage process for manufacturing synthetic teeth or crowns, other tooth parts using inlays or hardening dental materials. Here, the first stage includes: a composition containing (A) at least one multifunctional isocyanate compound, (B) at least one polyol compound, (C) at least one methacrylate monomer having at least two hydroxyl groups, (D) a catalyst for initiating polymerization of the methacrylate monomer using heat or light, and (E) a catalyst for promoting the formation of polyurethane by the above (A), (B) and (C), but not performing free radical polymerization of the above (C) is hardened at room temperature, a blank having rubber elasticity is manufactured, and the blank is formed and mechanically finished. In addition, the second stage includes: the above-mentioned formed blank having rubber elasticity is hardened to obtain the above-mentioned hard artificial teeth or artificial tooth parts.

[0005] When the two-stage process described above is used, the blank obtained by filling the composition into the tooth cavity and hardening in the first stage has elasticity, so the dentist can easily remove it from the cavity, and then directly perform the second stage hardening on the spot by light irradiation, etc. Therefore, the two-stage process described above is suitable for manufacturing a temporary crown or bridge material for temporary filling.

[0006] In addition, Patent Document 2 also discloses a two-stage process technology of forming a preform by polyaddition reaction and then hardening the preform into a harder molded body by free radical polymerization. Furthermore, Patent Document 2 also discloses that the molded body (molded body mainly made of polyurethane raw material) can be used for extremely various purposes.

[0007] Furthermore, Patent Document 3 proposes a dental restorative material comprising a polyurethane resin satisfying the following conditions I and II or a composite material using the resin.

[0008] Condition I: BS A ≥200(MPa)

[0009] Condition II: 1>BS W / BS A ≥0.7

[0010] Here, B.S. A Indicates the three-point bending strength (MPa) based on ISO 6872, BS W Indicates the three-point bending strength (MPa) after immersion in water based on JDMAS245:2017.

[0011] Here, when manufacturing the dental resin material for cutting composed of the above dental restorative material, the following method is used: the polymerizable composition to be the raw material is cast and then heated, and urethane bonds are formed and free radical polymerization is carried out during the heating process, thereby polymerizing and curing.

[0012] [Prior art literature]

[0013] [Patent Literature]

[0014] Patent Document 1: U.S. Patent No. 4787850

[0015] Patent Document 2: Japanese Patent, National Publication No. 2002-527588

[0016] Patent Document 3: Japanese Patent, Japanese Patent Publication No. 2019-210233 Summary of the invention

[0017] (Problems to be solved by the invention)

[0018] As disclosed in Patent Document 3, the material obtained by the method disclosed in Patent Document 1 or Patent Document 2 has polyurethane resin as the main component. Therefore, the material is excellent in strength, but depending on the type of polyurethane or the degree of progress of its reaction, the second stage of free radical polymerization is not fully carried out, which sometimes has an adverse effect on strength, especially water resistance. In contrast, the composite material disclosed in Patent Document 3 has high strength and has water resistance that maintains high strength even in a wet environment such as water.

[0019] However, when the inventors of the present application produced the composite material according to the method for producing the composite material disclosed in Patent Document 3, they found that the uniformity of the obtained hardened body was sometimes insufficient.

[0020] The present invention has been completed in view of the above situation, and its subject is to provide: a method for manufacturing a polyurethane composite material that can easily produce a hardened body that has excellent strength and water resistance as well as uniformity, and a polyurethane composite material and a dental cutting material that are manufactured using the method for manufacturing a polyurethane composite material and have excellent adhesion.

[0021] (Solutions to solve problems)

[0022] The above-mentioned problems are achieved by the following present invention.

[0023] The method for producing the polyurethane composite material of the present invention has the following characteristics.

[0024] The method for manufacturing the polyurethane composite material comprises:

[0025] a polyaddition reaction step of forming a polyurethane component (A) having a number average molecular weight of 1,500 to 5,000 and having a free radical polymerizable group by causing a polyaddition reaction between the diol compound (a1) and the diisocyanate compound (a2) in a polyaddition reactive raw material composition comprising a diol compound (a1) having one or more free radical polymerizable groups, a diisocyanate compound (a2), and a polymerizable monomer (B) having one or more free radical polymerizable groups in its molecule and not causing a polyaddition reaction with either the diol compound (a1) or the diisocyanate compound (a2);

[0026] a radical polymerizable raw material composition preparation step of preparing a radical polymerizable raw material composition comprising a polyurethane component (A), a polymerizable monomer (B), a radical polymerization initiator (C) and a filler (D);

[0027] A free radical polymerization step, after the addition polymerization step and the free radical polymerizable raw material composition preparation step are completed, free radical polymerization is performed using the free radical polymerizable raw material composition to form a polyurethane composite material;

[0028] The mixing ratio Rr of the polymerizable monomer represented by the following formula (1) is 20 wt % to 80 wt %.

[0029] Formula (1) Rr=100×Br / [a1r+a2r+Ar+Br]

[0030] In formula (1), a1r represents the content (parts by mass) of the unreacted diol compound (a1) remaining in the free radical polymerizable raw material composition, a2r represents the content (parts by mass) of the unreacted diisocyanate compound (a2) remaining in the free radical polymerizable raw material composition, Ar represents the content (parts by mass) of the polyurethane component (A) contained in the free radical polymerizable raw material composition, and Br represents the content (parts by mass) of the polymerizable monomer (B) contained in the free radical polymerizable raw material composition.

[0031] In an embodiment of the method for producing a polyurethane composite material of the present invention, the content of the filler (D) in the radical polymerizable raw material composition is preferably 60 wt % to 85 wt %.

[0032] In an embodiment of the method for producing a polyurethane composite material of the present invention, it is preferred that the polymerizable monomer (B) includes a polymerizable monomer represented by the following structural formula (1).

[0033] [Chemical formula 1]

[0034]

[0035] In the structural formula (1), R 11 and R 12 is a hydrogen atom or a methyl group, and n1 is an integer of 1 to 10.

[0036] In an embodiment of the method for producing a polyurethane composite material of the present invention, the diol compound (a1) preferably has 2 to 8 atoms constituting the main chain of the divalent organic residue between two hydroxyl groups contained in the diol compound.

[0037] In an embodiment of the method for producing a polyurethane composite material of the present invention, it is preferred that a thermal radical polymerization initiator is used as the radical polymerization initiator (C), and the radical polymerization step is carried out in a state heated to a temperature of -10°C to +25°C, which is the 10-hour half-life temperature of the thermal radical polymerization initiator.

[0038] In an embodiment of the method for producing a polyurethane composite material of the present invention, it is preferred that the addition-polymerization reactive raw material composition is prepared by further adding a diisocyanate compound (a2) to the primary raw material composition after preparing a primary raw material composition comprising a diol compound (a1), a polymerizable monomer (B) and a filler (D).

[0039] In an embodiment of the method for producing a polyurethane composite material of the present invention, it is preferred that the radical polymerizable raw material composition is a paste-like composition.

[0040] In an embodiment of the method for producing a polyurethane composite material of the present invention, it is preferred that the radical polymerization step is performed after the radical polymerizable raw material composition is injected into the mold frame.

[0041] The first polyurethane composite material of the present invention has the following characteristics.

[0042] The polyurethane composite material is manufactured through a polyaddition reaction step, a free radical polymerizable raw material composition preparation step, and a free radical polymerization step, wherein:

[0043] In the polyaddition reaction step, a polyurethane component (A) having a number average molecular weight of 1,500 to 5,000 and having a radical polymerizable group is formed by polyaddition reaction of the diol compound (a1) and the diisocyanate compound (a2) in a polyaddition reactive raw material composition comprising a diol compound (a1) having one or more radical polymerizable groups, a diisocyanate compound (a2), and a polymerizable monomer (B) having one or more radical polymerizable groups in its molecule and not undergoing a polyaddition reaction with either the diol compound (a1) or the diisocyanate compound (a2).

[0044] In the radical polymerizable raw material composition preparation step, a radical polymerizable raw material composition comprising a polyurethane component (A), a polymerizable monomer (B), a radical polymerization initiator (C) and a filler (D) is prepared.

[0045] In the radical polymerization step, after the addition polymerization step and the radical polymerizable raw material composition preparation step are completed, the radical polymerizable raw material composition is used to perform radical polymerization to form a polyurethane composite material;

[0046] The mixing ratio Rr of the polymerizable monomer represented by the following formula (1) is 20 wt% to 80 wt%, the content ratio of the filler (D) in the radical polymerizable raw material composition is 60 wt% to 85 wt%, a thermal radical polymerization initiator is used as the radical polymerization initiator (C), and the radical polymerization process is carried out in a state where the composition is heated to a temperature of -10°C to +25°C which is the 10-hour half-life temperature of the thermal radical polymerization initiator. In the copolymer of the polyurethane component (A) and the polymerizable monomer (B) formed in the radical polymerization process, 10% to 25% of the total amount of radical polymerizable groups possessed by the diol compound (a1) and the polymerizable monomer (B) contained in the radical polymerizable raw material composition remain.

[0047] Formula (1) Rr=100×Br / [a1r+a2r+Ar+Br]

[0048] In formula (1), a1r represents the content (parts by mass) of the unreacted diol compound (a1) remaining in the free radical polymerizable raw material composition, a2r represents the content (parts by mass) of the unreacted diisocyanate compound (a2) remaining in the free radical polymerizable raw material composition, Ar represents the content (parts by mass) of the polyurethane component (A) contained in the free radical polymerizable raw material composition, and Br represents the content (parts by mass) of the polymerizable monomer (B) contained in the free radical polymerizable raw material composition.

[0049] The second polyurethane composite material of the present invention has the following characteristics.

[0050] The polyurethane composite material is composed of a composite material including a polyurethane resin matrix and fillers dispersed in the polyurethane resin matrix. The polyurethane resin matrix is ​​composed of a copolymer of a polyurethane having a number average molecular weight of 1500 to 5000 and having a free radical polymerizable group and a free radical polymerizable monomer that does not undergo addition polymerization reaction with a hydroxyl group and an isocyanate group. The content of free radical polymerizable carbon-carbon double bonds contained in each 1g of the polyurethane resin matrix is ​​0.5mmol / g to 1.0mmol / g, and the content of the fillers in the composite material is 60wt% to 85wt%.

[0051] The dental cutting material of the first present invention has the following characteristics.

[0052] The dental cutting material is composed of a polyurethane composite material, which is manufactured through a polyaddition reaction step, a free radical polymerizable raw material composition preparation step, and a free radical polymerization step.

[0053] In the polyaddition reaction step, a polyurethane component (A) having a number average molecular weight of 1,500 to 5,000 and having a radical polymerizable group is formed by polyaddition reaction of the diol compound (a1) and the diisocyanate compound (a2) in a polyaddition reactive raw material composition comprising a diol compound (a1) having one or more radical polymerizable groups, a diisocyanate compound (a2), and a polymerizable monomer (B) having one or more radical polymerizable groups in its molecule and not undergoing a polyaddition reaction with either the diol compound (a1) or the diisocyanate compound (a2).

[0054] In the radical polymerizable raw material composition preparation step, a radical polymerizable raw material composition comprising a polyurethane component (A), a polymerizable monomer (B), a radical polymerization initiator (C) and a filler (D) is prepared.

[0055] In the radical polymerization step, after the addition polymerization step and the radical polymerizable raw material composition preparation step are completed, the radical polymerizable raw material composition is used to perform radical polymerization to form a polyurethane composite material;

[0056] The mixing ratio Rr of the polymerizable monomer represented by the following formula (1) is 20 wt% to 80 wt%, the content ratio of the filler (D) in the radical polymerizable raw material composition is 60 wt% to 85 wt%, a thermal radical polymerization initiator is used as the radical polymerization initiator (C), and the radical polymerization process is carried out in a state where the composition is heated to a temperature of -10°C to +25°C which is the 10-hour half-life temperature of the thermal radical polymerization initiator. In the copolymer of the polyurethane component (A) and the polymerizable monomer (B) formed in the radical polymerization process, 10% to 25% of the total amount of radical polymerizable groups possessed by the diol compound (a1) and the polymerizable monomer (B) contained in the radical polymerizable raw material composition remain.

[0057] Formula (1) Rr=100×Br / [a1r+a2r+Ar+Br]

[0058] In formula (1), a1r represents the content (parts by mass) of the unreacted diol compound (a1) remaining in the free radical polymerizable raw material composition, a2r represents the content (parts by mass) of the unreacted diisocyanate compound (a2) remaining in the free radical polymerizable raw material composition, Ar represents the content (parts by mass) of the polyurethane component (A) contained in the free radical polymerizable raw material composition, and Br represents the content (parts by mass) of the polymerizable monomer (B) contained in the free radical polymerizable raw material composition.

[0059] The dental cutting material of the second present invention has the following characteristics.

[0060] The dental cutting material is composed of a polyurethane composite material, which is composed of a composite material including a polyurethane resin matrix and fillers dispersed in the polyurethane resin matrix. The polyurethane resin matrix is ​​composed of a copolymer of a polyurethane having a number average molecular weight of 1500 to 5000 and a free radical polymerizable group and a free radical polymerizable monomer that does not undergo addition polymerization reaction with hydroxyl groups and isocyanate groups. The content of free radical polymerizable carbon-carbon double bonds contained in each 1g of the polyurethane resin matrix is ​​0.5mmol / g to 1.0mmol / g, and the content of the filler in the composite material is 60wt% to 85wt%.

[0061] (Effects of the Invention)

[0062] As described above, according to the present invention, there can be provided: a method for producing a polyurethane composite material that can easily produce a hardened body that has excellent strength and water resistance as well as uniformity, and a polyurethane composite material and a dental cutting material that are produced using the method for producing a polyurethane composite material and have excellent adhesion. DETAILED DESCRIPTION

[0063] Hereinafter, the method for manufacturing the polyurethane composite material of the present embodiment, the polyurethane composite material of the present embodiment, and the dental cutting material of the present embodiment are described. It should be noted that, in the present application specification, unless otherwise specified, the description method of "x to y" using the numerical values ​​x and y means "above x and below y". When a unit is added only to the numerical value y in this description method, the unit also applies to the numerical value x. In addition, in the present application specification, the term "(meth) propylene" means both "propylene" and "meth propylene".

[0064] 1. Method for manufacturing polyurethane composite materials

[0065] The method for producing the polyurethane composite material of this embodiment has the following characteristics:

[0066] The manufacturing method comprises:

[0067] A polyaddition reaction step of forming a polyurethane component (A) having a number average molecular weight of 1,500 to 5,000 and having a free radical polymerizable group by causing a polyaddition reaction between the diol compound (a1) and the diisocyanate compound (a2) in a polyaddition reactive raw material composition comprising a diol compound (a1) having one or more free radical polymerizable groups, a diisocyanate compound (a2), and a polymerizable monomer (B) having one or more free radical polymerizable groups in its molecule and not causing a polyaddition reaction with either the diol compound (a1) or the diisocyanate compound (a2);

[0068] A radical polymerizable raw material composition preparation step of preparing a radical polymerizable raw material composition comprising a polyurethane component (A), a polymerizable monomer (B), a radical polymerization initiator (C) and a filler (D);

[0069] A free radical polymerization step, after completing the addition polymerization step and the free radical polymerizable raw material composition preparation step, by using the free radical polymerizable raw material composition to perform free radical polymerization to form a polyurethane composite material, and

[0070] The mixing ratio Rr of the polymerizable monomer represented by the following formula (1) is 20 wt % to 80 wt %.

[0071] Formula (1) Rr=100×Br / [a1r+a2r+Ar+Br]

[0072] In formula (1), a1r represents the content (parts by mass) of the unreacted diol compound (a1) remaining in the free radical polymerizable raw material composition, a2r represents the content (parts by mass) of the unreacted diisocyanate compound (a2) remaining in the free radical polymerizable raw material composition, Ar represents the content (parts by mass) of the polyurethane component (A) contained in the free radical polymerizable raw material composition, and Br represents the content (parts by mass) of the polymerizable monomer (B) contained in the free radical polymerizable raw material composition.

[0073] In addition, in the following description, a diol compound having one or more free radical polymerizable groups is sometimes referred to as a "free radical polymerizable diol compound", a polyurethane component having a number average molecular weight of 1500 to 5000 and having a free radical polymerizable group is referred to as a "free radical polymerizable polyurethane component", and a polymerizable monomer having one or more free radical polymerizable groups in the molecule and not undergoing addition polymerization reaction with the diol compound (a1) and the diisocyanate compound (a2) is referred to as a "non-addition polymerizable free radical polymerizable monomer".

[0074] According to the manufacturing method of the polyurethane composite material of the present embodiment, a hardened body (polyurethane composite material) having excellent strength, water resistance and uniformity can be easily manufactured. The reason for obtaining such an effect cannot be clearly determined, but the inventors of the present application speculate as follows.

[0075] First, in the method for producing the polyurethane composite material of the present embodiment, when free radical polymerization is performed, the free radical polymerizable groups of the components having free radical polymerizable groups (i.e., free radical polymerizable polyurethane component (A) and non-addition polymerizable free radical polymerizable monomer (B)) react with each other. In addition, the molecular size of the free radical polymerizable polyurethane component (A) used in the free radical polymerization is controlled to an appropriate size corresponding to a number average molecular weight of 1500 to 5000. It is therefore believed that when free radical polymerization is performed, many crosslinking points are easily formed, and as a result, the strength and water resistance of the polyurethane composite material obtained by free radical polymerization are improved.

[0076] In addition, in the technology disclosed in patent document 1, in the polyaddition reaction process, in addition to isocyanates and polyols as general polyurethane precursor components, methacrylate monomers (polyurethane precursor components and polymerizable monomers) having two or more hydroxyl groups as the third main component are also added to the polyaddition reaction. In addition, in the technology disclosed in patent document 2, as polyurethane precursor components, isocyanato and monomers having hydroxyl groups and free radical polymerizable groups (polyurethane precursor components and free radical polymerizable monomers) participate in the polyaddition reaction. That is, in the technology disclosed in patent documents 1 and 2, free radical polymerizable monomers are included as part of the polyurethane component (relatively large molecules) formed by the polyaddition reaction. Therefore, as a result, in the free radical polymerization process as the next process, the formation of crosslinking points using free radical polymerizable groups will be limited.

[0077] However, in the method for manufacturing the polyurethane composite material of the present embodiment, the non-addition-polymerizable free radical polymerizable monomer (B) contained in the addition-polymerization reactive raw material composition used in the addition-polymerization process is not added to the addition-polymerization reaction. Therefore, in the free radical polymerization process as the next process, it is easy to make the non-addition-polymerizable free radical polymerizable monomer (B) approach the free radical polymerizable group of the free radical polymerizable polyurethane component (A) which is a relatively large molecule and undergo free radical polymerization, thereby, the formation of crosslinking points based on free radical polymerization is not easily hindered. Based on this reason, it can be considered that: compared with the technology disclosed in patent documents 1 and 2, the method for manufacturing the polyurethane composite material of the present embodiment can more easily obtain a polyurethane composite material with excellent strength and water resistance.

[0078] On the other hand, the inventors of the present application have studied the reason why the uniformity of the hardened body manufactured in the technology disclosed in patent document 3 is reduced. As a result, it is clear that the uniformity of the hardened body is related to the control state of addition polymerization and free radical polymerization. That is, in the technology disclosed in patent document 3, addition polymerization and free radical polymerization are implemented in parallel at the same time over time, so it is not easy to control the two reactions separately and independently. In this way, since it is not easy to control the reactivity of the two reactions, it can be considered that in the technology disclosed in patent document 3, the uniformity of the hardened body is easily reduced due to the occurrence of polymerization shrinkage, etc. Based on this point, in the manufacturing method of the polyurethane composite material of the present embodiment, by implementing the free radical polymerization process after the addition polymerization process ends, the addition polymerization and free radical polymerization are separately and independently controlled. Therefore, it is easy to ensure the uniformity of the obtained hardened body.

[0079] Hereinafter, various raw materials and steps used in the method for producing the polyurethane composite material according to the present embodiment will be described in detail.

[0080] 2. Various raw materials used in the manufacturing method of polyurethane composite materials

[0081] 2-1. Radically polymerizable diol compound (a1)

[0082] The radical polymerizable diol compound (a1) is a compound that serves as a raw material for forming the radical polymerizable polyurethane component (A). The radical polymerizable polyurethane component (A) is formed by causing two hydroxyl groups of the radical polymerizable diol compound (a1) and the isocyanate group of the other diisocyanate compound (a2) as a polyurethane precursor component to undergo an addition polymerization reaction in the addition polymerization reaction step.

[0083] As the radical polymerizable diol compound (a1), a compound having at least one radical polymerizable group and two hydroxyl groups in the molecule can be used without particular limitation. Here, the radical polymerizable group refers to a functional group that reacts and polymerizes with an initiator that generates free radicals, specifically, a group having a radical polymerizable carbon-carbon double bond such as a vinyl group, a (meth)acrylate group, and a styrene group.

[0084] The free radical polymerizable groups are introduced into the main chain of the polyurethane molecule formed by the addition polymerization reaction of the diol compound with free radical polymerizable groups. In addition, during the free radical polymerization in the free radical polymerization step, the free radical polymerizable groups in the molecules of the free radical polymerizable polyurethane component (A) react with each other, or the free radical polymerizable groups in the molecules of the free radical polymerizable polyurethane component (A) and the free radical polymerizable groups of the non-addition free radical polymerizable monomer (B) react to form bonds, thereby forming crosslinks. As a result, the water resistance of the polyurethane composite material as a hardened body is improved.

[0085] As the radical polymerizable polyurethane component (A), the radical polymerizable group is preferably a (meth)acrylate group from the viewpoint of being able to form (meth)acrylic urethane ester, wherein the (meth)acrylic urethane ester is able to form hydrogen bonds and improve toughness. From the viewpoint of the strength and water resistance of the resultant polyurethane composite material, the number of radical polymerizable groups contained in the molecule of the radical polymerizable diol compound (a1) is preferably 1 to 4, and particularly preferably 1 to 2. When the number of radical polymerizable groups is 4 or less, the shrinkage of the hardened body formed during the radical polymerization reaction can be more easily suppressed.

[0086] In addition, the number of atoms constituting the main chain of the divalent organic residue between two hydroxyl groups included in the molecule of the radical polymerizable diol compound (a1) (hereinafter sometimes referred to as "OH distance") is preferably 2 to 8, more preferably 2 to 6, and particularly preferably 2 to 4. By setting the OH distance of the radical polymerizable diol compound (a1) to be within the above range, not only can the radical polymerizable groups be introduced into the molecules of the radical polymerizable polyurethane component (A) obtained in the addition polymerization step at a high density, but also the strength of the polyurethane composite material can be easily maintained and the adhesiveness can be improved.

[0087] In addition, when two or more types of free radical polymerizable diol compounds (a1) are used, the distance between OH represents a value calculated as the average value of the two or more types of free radical polymerizable diol compounds (a1). Here, when n types of free radical polymerizable diol compounds (a1) are used, the average value of the distance between OH is calculated based on the following formula (2).

[0088] [Formula 1]

[0089] Formula (2)

[0090] In formula (2), n represents an integer greater than 2, x represents an integer in the range of 1 to n, Dx represents the OH distance of the x-th type of radically polymerizable diol compound (a1), and Mx represents the molar fraction (mole / mole) of the x-th radically polymerizable diol compound (a1) when the total amount of the 1st to n-th radically polymerizable diol compounds (a1) is set to 1 mole.

[0091] Examples of compounds suitable for use as the radical polymerizable diol compound (a1) include trimethylolpropane mono(meth)acrylate, glycerol mono(meth)acrylate, pentaerythritol di(meth)acrylate, and acid ((meth)acrylic acid or vinyl benzoic acid) ring-opened products of ethylene glycol diglycidyl ether. These compounds may be used alone or in combination.

[0092] 2-2. Diisocyanate compound (a2)

[0093] The diisocyanate compound (a2) is another polyurethane precursor component for forming the radically polymerizable polyurethane component (A), and any known compound having two isocyanate groups in one molecule can be used without particular limitation.

[0094] Examples of compounds suitable for use as the diisocyanate compound (a2) include 1,3-bis(2-isocyanato-2-propyl)benzene, 2,2-bis(4-isocyanatophenyl)hexafluoropropane, 1,3-bis(isocyanatomethyl)cyclohexane, 4,4'-methylenediphenyl diisocyanate, 3,3'-dichloro-4,4'-diisocyanato biphenyl, and 4,4'-diisocyanato-3,3'-dimethyl biphenyl. biphenyl), dicyclohexylmethane-4,4'-diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanato, norbornane diisocyanate, diisocyanic acid isophorone, 1,5-diisocyanato naphthalene, diisocyanic acid 1,3-phenylene, trimethylhexamethylene diisocyanato, tolylene-2,4-diisocyanato, tolylene-2,6-diisocyanato, m-xylene diisocyanato, etc.

[0095] Among them, as the diisocyanate compound (a2), from the viewpoint of the handleability of the radical polymerizable raw material composition and the strength of the obtained polyurethane composite material, a diisocyanate compound (a2) having a phenyl group in the molecule is preferred, and m-xylene diisocyanate is particularly preferred.

[0096] The amount of the radical polymerizable diol compound (a1) and the diisocyanate compound (a2) used in the polyaddition reaction step is not particularly limited as long as the molar ratio [the amount of diisocyanate compound (a2) used / the amount of radical polymerizable diol compound (a1) used] is about 1 mol / mol, but generally, it is preferably about 0.9 to 1.2 mol / mol. In addition, from the viewpoint that the radical polymerizable diol compound (a1) and the diisocyanate compound (a2) react quantitatively to form the radical polymerizable polyurethane component (A) in the polyaddition reaction step and that unreacted products are minimized, the molar ratio is preferably 1.0 to 1.1 mol / mol.

[0097] 2-3. Radically polymerizable polyurethane component (A)

[0098] The radical polymerizable polyurethane component (A) is a component formed by subjecting a radical polymerizable diol compound (a1) and a diisocyanate compound (a2) to a polyaddition reaction in a polyaddition reaction step. The structure of the radical polymerizable polyurethane component (A) is almost uniquely determined based on the radical polymerizable diol compound (a1) and the diisocyanate compound (a2) used in the polyaddition reaction step.

[0099] In addition, regarding the free radical polymerizable polyurethane component (A), it is also a component of the polyurethane resin matrix in the polyurethane composite material as the final product by free radical polymerization with the non-addition polymerizable free radical polymerizable monomer (B) using the catalytic action of the free radical polymerization initiator (C). Therefore, the component that mainly includes the components remaining after excluding the filler (D) from the free radical polymerizable raw material composition, in other words, the free radical polymerizable polyurethane component (A), the non-addition polymerizable free radical polymerizable monomer (B), and the free radical polymerization initiator (C) can be called the matrix raw material composition. It should be noted that when the free radical polymerizable raw material composition further includes a fifth component other than components A to D, when the fifth component is dissolved in the free radical polymerizable polyurethane component (A) and / or the non-addition polymerizable free radical polymerizable monomer (B), the fifth component also constitutes the matrix raw material composition.

[0100] The number average molecular weight of the radically polymerizable polyurethane component (A) contained in the radically polymerizable raw material composition is 1500 to 5000. By setting the number average molecular weight to be above 1500, a polyurethane composite material with sufficient strength can be obtained. On the other hand, the inventors of the present application have made various attempts on the following situations, but have not been able to obtain a radically polymerizable polyurethane component (A) with a number average molecular weight exceeding 5000, wherein the situation refers to: in an addition-polymerizable raw material composition in which the content of the non-addition-polymerizable radically polymerizable monomer (B) is modulated to various values, a radically polymerizable polyurethane component (A) with a number average molecular weight exceeding 5000 is obtained by causing a diol compound (a1) and a diisocyanate compound (a2) to undergo an addition polymerization reaction. Therefore, from the viewpoint of manufacturability and practicality, the number average molecular weight only needs to be below 5000. It should be noted that, when the number average molecular weight is made smaller within the range of 1500 to 5000, the precipitation of the radical polymerizable polyurethane component (A) in the matrix raw material composition can be more reliably suppressed, so that uniform radical polymerization can be performed more easily. Moreover, when the radical polymerizable raw material composition is in a paste state, the fluidity of the radical polymerizable raw material composition is also improved and the viscosity is reduced, so that the operability is further improved. From the perspective of making the operability of the radical polymerizable raw material composition and the strength of the polyurethane composite material coexist (both) in a more balanced manner, the above number average molecular weight is preferably 1500 to 3500, more preferably 1700 to 3300, and particularly preferably 2000 to 3000. In addition, with respect to the radical polymerizable polyurethane component (A), it is preferred that: at least at the temperature of the radical polymerization reaction in the radical polymerization step, the non-addition polymerizable radical polymerizable monomer (B) can be dissolved in the matrix raw material composition.

[0101] It should be noted that in the manufacturing method of the polyurethane composite material of the present embodiment, the following situation will not occur: in the addition reaction in the addition reaction process, the non-addition polymerizable free radical polymerizable monomer (B) that does not participate in the addition reaction plays a role as a solvent, thereby forming a high molecular weight polyurethane that becomes a precipitate. In addition, the presence of the non-addition polymerizable free radical polymerizable monomer (B) that plays a role as a solvent will affect the collision frequency (reaction opportunity) of the free radical polymerizable diol compound (a1) and the diisocyanate compound (a2) present in the reaction system, therefore, by adjusting the mixing amount of the non-addition polymerizable free radical polymerizable monomer (B) contained in the addition reaction raw material composition, the number average molecular weight can be adjusted to the above range. In this case, if the content ratio of the non-addition polymerizable free radical polymerizable monomer (B) contained in the addition reaction raw material composition is increased, the number average molecular weight can be reduced, and if the content ratio is reduced, the number average molecular weight can be increased.

[0102] In addition, the number average molecular weight of the radical polymerizable polyurethane component (A) refers to the number average molecular weight converted to polystyrene determined by GPC (Gel Permeation Chromatography). The number average molecular weight of the radical polymerizable polyurethane component (A) in the radical polymerizable raw material composition can be obtained by the following method, which means: as needed, a solvent such as THF (tetrahydrofuran) is added to the radical polymerizable raw material composition, and insoluble components such as filler (D) are removed by filtering, centrifugation, etc., and the resulting solution (i.e., a matrix raw material composition, or a solution composed of a mixture of the matrix raw material composition and a solvent added as needed) is measured by GPC. The measurement can be performed using an advanced polymer chromatograph (manufactured by Waters Corporation, Japan) and under the following measurement conditions.

[0103] [Measurement conditions]

[0104]

[0105] Column temperature: 40°C

[0106] Developing solvent: THF

[0107] Flow rate: 0.5ml / min

[0108] Detector: Photodiode array detector 254nm (PDA detector)

[0109] 2-4. Non-addition polymerizable free radical polymerizable monomer (B)

[0110] The non-addition-polymerizable free radical polymerizable monomer (B) is a compound having at least one free radical polymerizable group in the molecule and not undergoing addition polymerization reaction with the free radical polymerizable diol compound (a1) and the diisocyanate compound (a2). Here, "not undergoing addition polymerization reaction with the free radical polymerizable diol compound (a1) and the diisocyanate compound (a2)" means: the molecule does not contain both a group that undergoes addition polymerization reaction with the free radical diol compound (a1) and a group that undergoes addition polymerization reaction with the diisocyanate compound (a2), specifically, it means: it does not contain a hydroxyl group, an amino group, a carboxyl group, an isocyanate group, and a mercapto group. Among these functional groups, the group that can undergo addition polymerization reaction with the free radical polymerizable diol compound (a1) can include an isocyanate group; the group that can undergo addition polymerization reaction with the diisocyanate compound (a2) can include a hydroxyl group, an amino group, a carboxyl group, and a mercapto group. Therefore, the non-addition polymerizable free radical polymerizable monomer (B) does not have a hydroxyl group, an amino group, a carboxyl group, an isocyanate group, and a thiol group in the molecule. In addition, the free radical polymerizable group can utilize the same group as the free radical polymerizable group possessed by the free radical polymerizable diol compound (a1). As a suitable free radical polymerizable group, preferably: a (meth) acrylate group and / or a (meth) acrylamide group or a group having the same molecular structure as the free radical polymerizable group possessed by the free radical polymerizable diol compound (a1). Regarding the number of free radical polymerizable groups contained in the molecule of the non-addition polymerizable free radical polymerizable monomer (B), from the viewpoint of easy formation of crosslinks, preferably 2 to 6, more preferably 2 to 4. By making the number of free radical polymerizable groups 2 or more, the crosslinking density can be made larger, and therefore, a hardened body with sufficient strength can be obtained more easily. In addition, by making the number of free radical polymerizable groups 6 or less, it is easier to suppress shrinkage during hardening. In addition, the non-addition-polymerizable radical polymerizable monomer (B) is preferably a liquid at room temperature (ie, 25° C.).

[0111] The non-addition-polymerizable free radical polymerizable monomer (B) in the addition-polymerizable raw material composition does not participate in the addition-polymerization reaction in the addition-polymerization reaction process, but acts as a solvent. Therefore, the number average molecular weight of the free radical polymerizable polyurethane component (A) formed in the addition-polymerization reaction process can be adjusted to be within the range of 1500 to 5000 very easily. In addition, with respect to the non-addition-polymerizable free radical polymerizable monomer (B) in the free radical polymerizable raw material composition, (i) when the phase morphology of the free radical polymerizable raw material composition is in a paste state, the dispersion of the free radical polymerizable polyurethane component (A) is promoted, thereby contributing to improving the operability of the free radical polymerizable raw material composition, and (ii) in the free radical polymerization process, a part of the non-addition-polymerizable free radical polymerizable monomer (B) reacts with the free radical polymerizable group of the free radical polymerizable polyurethane component (A) to form a bond, which also contributes to the formation of crosslinking points.

[0112] The viscosity of the non-addition-polymerizable free radical polymerizable monomer (B) is not particularly limited, but is preferably in the range of 1 mPa·s to 1000 mPa·s at room temperature, and more preferably in the range of 1 mPa·s to 100 mPa·s. When the phase morphology of the free radical polymerizable raw material composition is a paste, the use of a non-addition-polymerizable free radical polymerizable monomer (B) having a viscosity in the above range can further improve the operability of the free radical polymerizable raw material composition.

[0113] As the non-addition-polymerizable radical polymerizable monomer (B), it is preferred that the polymerizable monomer (B) contains a monomer represented by the following structural formula (1) because the number average molecular weight of the radical polymerizable polyurethane component (A) can be easily adjusted to within the range of 1500 to 5000.

[0114] [Chemical formula 2]

[0115]

[0116] In addition, in the structural formula (1), R 11 and R 12 represents a hydrogen atom or a methyl group, and n1 represents an integer of 1 to 10, preferably an integer of 1 to 3.

[0117] Examples of compounds that can be suitably used as the non-addition polymerizable free radical polymerizable monomer (B) include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol methacrylate, polypropylene glycol methacrylate, tricyclodecanol methacrylate, trimethylolpropane methacrylate, pentaerythritol methacrylate, ditrimethylolpropane methacrylate, and dipentaerythritol methacrylate. Among them, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, and triethylene glycol di(meth)acrylate are particularly preferred.

[0118] The content of the non-additive free radical polymerizable monomer (B) in the free radical polymerizable raw material composition requires that the polymerizable monomer mixing ratio Rr shown in formula (1) is 20wt% to 80wt%. By making the polymerizable monomer mixing ratio Rr below 80wt%, the content ratio of the free radical polymerizable polyurethane component (A) that helps to improve the strength becomes larger, so that a polyurethane composite material with sufficient strength can be obtained. In addition, by making the polymerizable monomer mixing ratio Rr above 20wt%, the homogeneity of the free radical polymerizable raw material composition is improved, as a result, a hardened body with excellent uniformity and suppressed hardening unevenness of the obtained hardened body can be obtained. Moreover, when the phase morphology of the free radical polymerizable raw material composition is in a paste state, its operability can also be easily improved. From the viewpoint of making the suppression of hardening unevenness of the hardened body and the strength of the hardened body coexist (both) in a more balanced manner, the polymerizable monomer mixing ratio Rr is preferably 20wt% to 50wt%, and more preferably 20wt% to 35wt%. Furthermore, from the viewpoint of being able to easily obtain a polyurethane composite material having excellent adhesiveness, the polymerizable monomer mixing ratio Rr is particularly preferably 20 wt % to 35 wt %.

[0119] 2-5. Radical polymerization initiator (C)

[0120] The radical polymerization initiator (C) has the function of initiating a radical polymerization reaction in the radical polymerization process, and has the function of polymerizing and curing the radical polymerizable raw material composition and forming crosslinking points by reacting and combining the radical polymerizing groups with each other. As the radical polymerization initiator (C), a thermal radical polymerization initiator and / or a photoradical polymerization initiator can be used, but from the viewpoint of being able to uniformly cure to the inside of the radical polymerizable raw material composition, a thermal radical polymerization initiator is preferably used. As a thermal polymerization initiator, from the viewpoint of easy handling or stability, a thermal polymerization initiator having a 10-hour half-life temperature in the range of 40°C to 150°C is preferred, and a thermal polymerization initiator having a 10-hour half-life temperature in the range of 70°C to 100°C is particularly preferred. Here, the 10-hour half-life temperature refers to the temperature at which the amount of the thermal polymerization initiator present is reduced to half of the initial amount after 10 hours from the initial period, and is used as an indicator of the reactivity of the thermal polymerization initiator. Specific examples of thermal free radical polymerization initiators that can be suitably used include peroxide initiators such as benzoyl peroxide and tert-butylperoxylaurate, azo initiators such as azobisbutyronitrile and azobis(2,4-dimethylvaleronitrile), etc. These thermal polymerization initiators can be used alone or in combination of two or more.

[0121] The amount of the radical polymerization initiator (C) used can be appropriately determined depending on the type thereof, and is generally preferably in the range of 0.005 wt% to 2.0 wt%, more preferably 0.01 wt% to 1.0 wt%, based on the mass of the matrix raw material composition.

[0122] 2-6. Filler (D)

[0123] The filler (D) has the function of improving the physical properties of the polyurethane composite material, such as mechanical strength, wear resistance and water resistance, by being dispersed in the polyurethane resin matrix and forming a composite with the polyurethane resin matrix.

[0124] As filler (D), preferably use inorganic fillers such as silica, alumina, titania, zirconia, or composite oxides thereof, glass, etc. Specific examples of such inorganic fillers include spherical particles or amorphous particles of amorphous silica, silica-zirconia, silica-titania, silica-titania-zirconia, quartz, alumina, etc. In addition, when the polyurethane composite material manufactured by the manufacturing method of the polyurethane composite material of the present embodiment is used as a dental material, as filler (D), preferably use silica, titania, zirconia, or composite oxides thereof, especially preferably silica or its composite oxide. This is because: these inorganic fillers have no danger of dissolving in the oral environment, are easy to adjust the refractive index difference with the polyurethane resin matrix, and are easy to control transparency or aesthetics.

[0125] The shape of the filler (D) is not particularly limited and can be appropriately selected according to the purpose of the target polyurethane composite material. For example, from the perspective of obtaining a polyurethane composite material with particularly excellent wear resistance, surface smoothness and gloss persistence, it is preferably spherical. In addition, polyurethane composite materials containing spherical fillers (D) are dispersed, which are also particularly suitable for dental use. The spherical shape mentioned here refers to: the average uniformity obtained in the image analysis of the image taken by a scanning or transmission electron microscope is above 0.6. The average uniformity is more preferably above 0.7, and further preferably above 0.8. The average uniformity can be calculated by the following method, which refers to: in the image analysis of the image taken by a scanning or transmission electron microscope, for n particles (usually more than 40, preferably more than 100), the long diameter (L) as the maximum diameter and the short diameter (B) orthogonal to the long diameter (L) are measured respectively, and the ratio (B / L) is obtained, and the sum (ΣB / L) is divided by n.

[0126] The average particle size of the filler (D) is preferably 0.001 μm to 100 μm, and more preferably 0.01 μm to 10 μm, from the viewpoint of wear resistance, surface smoothness, and gloss persistence. In addition, from the viewpoint of easily increasing the content of the filler (D) in the polyurethane composite material, it is preferred to use a filler (D) having a plurality of particle sizes. Specifically, it is preferred to combine a particle size of 0.001 μm to 0.1 μm and a particle size of 0.1 μm to 100 μm, and it is more preferred to combine a particle size of 0.01 μm to 0.1 μm and a particle size of 0.1 μm to 10 μm.

[0127] As filler (D), from the viewpoint of making the compatibility with the polyurethane resin matrix better and improving the mechanical strength or water resistance of the polyurethane composite material, it is preferred to use a filler after surface treatment. As a surface treatment agent, a silane coupling agent is usually used, especially for a filler (D) based on an inorganic particle system of silicon dioxide, as a silane coupling agent with a high effect of surface treatment based on a silane coupling agent, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, 3-methacryloyloxypropyl trimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc. are suitably used.

[0128] The amount of filler (D) used can be appropriately determined according to the physical properties of the target polyurethane composite material such as strength, but from the viewpoint of high strength of the polyurethane composite material, when expressed in wt% (hereinafter, sometimes referred to as filling rate) based on the mass of the free radical polymerizable raw material composition, it is preferably 60wt% to 85wt%, and more preferably 65wt% to 80wt%. In addition, the filling rate when the polyurethane composite material manufactured by the manufacturing method of the polyurethane composite material of the present embodiment is used as a dental cutting material is more preferably 65wt% to 80wt%, and further preferably 70wt% to 80wt%.

[0129] In addition, the inventors of this application have attempted to use the technology disclosed in Patent Document 3 to manufacture a polyurethane composite material having a mixed amount of filler (D) exceeding 60wt%. However, even if a paste-like raw material composition prepared to manufacture such a polyurethane composite material is used, the time in which the raw material composition is in a paste-like state suitable for injection into a mold frame is very short. Moreover, in this case, it is not easy to inject the raw material composition into the mold frame to form a desired shape, or, even if the raw material composition can be injected into the mold frame, it cannot be fully degassed, and therefore, a uniform hardened body cannot be obtained. However, when the manufacturing method of the polyurethane composite material of this embodiment and the forming method using the mold frame are combined, a uniform hardened body can be easily manufactured even for a polyurethane composite material with a high filling rate exceeding 60wt%.

[0130] 2-7. Other additives

[0131] In addition to the essential components described above, various other additives may be mixed into the free radical polymerizable raw material composition or the addition polymerization reactive raw material composition. Various additives include polymerization inhibitors, fluorescent agents, ultraviolet light absorbers, antioxidants, pigments, antibacterial materials, X-ray contrast agents, etc., and the amount thereof added may be appropriately determined according to the desired purpose.

[0132] 3. Each step of the method for producing a polyurethane composite material

[0133] The method for producing the polyurethane composite material of the present embodiment includes a polyaddition reaction step, a radical polymerizable raw material composition preparation step, and a radical polymerization step. Each step will be described in detail below.

[0134] 3-1. Polyaddition reaction step

[0135] (1) Preparation of Addition Polymerization Reactive Raw Material Composition

[0136] In the addition polymerization step, first, an addition polymerization reactive raw material composition containing a radically polymerizable diol compound (a1), a diisocyanate compound (a2), and a non-additionally polymerizable radically polymerizable monomer (B) is prepared. Then, a radically polymerizable diol compound (a1) and a diisocyanate compound (a2) are subjected to an addition polymerization reaction in the addition polymerization reactive raw material composition to form a radically polymerizable polyurethane component (A).

[0137] In addition, the addition-polymerization raw material composition may further include other components other than the above-mentioned three kinds of components. For example, when the filling rate of the filler (D) included in the free radical polymerizable raw material composition is high (for example, when the filling rate is about 60wt% or more), from the first viewpoint of ensuring the uniformity of the obtained hardened body or in the process of modulating the addition-polymerization raw material composition and the free radical polymerizable raw material composition, it is easier to ensure the operability of these raw material compositions, (i) the addition-polymerization raw material composition, preferably: in addition to the free radical polymerizable diol compound (a1), the diisocyanate compound (a2) and the non-addition polymerizable free radical polymerizable monomer (B), it also includes the filler (D). In addition, from the above-mentioned first viewpoint and the second viewpoint that the free radical polymerizable raw material composition can also be modulated while completing the addition reaction, (ii) the addition-polymerization raw material composition, more preferably, in addition to the free radical polymerizable diol compound (a1), the diisocyanate compound (a2) and the non-addition polymerizable free radical polymerizable monomer (B), it also includes a free radical polymerization initiator (C) and a filler (D). When the addition polymerizable raw material composition is in the embodiment shown in (ii) above, the addition polymerizable reaction step and the radical polymerizable raw material composition preparation step can be completed simultaneously.

[0138] In addition, the preparation steps of the addition polyreactive raw material composition are not particularly limited, and the preparation can be performed in any preparation steps. As the preparation steps of the addition polyreactive raw material composition, there can be mentioned (a) a one-step preparation method or (b) a multi-step preparation method, wherein in the one-step preparation method, the addition polyreactive raw material composition is prepared by mixing all the components constituting the addition polyreactive raw material composition at once; in the multi-step preparation method, after preparing a mixed composition in which a part of the components constituting the addition polyreactive raw material composition is mixed, the remaining components constituting the addition polyreactive raw material composition are added or mixed to the mixed composition at once, or the remaining components constituting the addition polyreactive raw material composition are added or mixed in succession in multiple times, thereby preparing the addition polyreactive raw material composition. As for which preparation method to be adopted, it can be appropriately selected after comprehensively considering the composition or operability of the addition polyreactive raw material composition to be prepared, the compatibility of the components constituting the addition polyreactive raw material composition, the working efficiency when preparing the addition polyreactive raw material composition, etc.

[0139] The mixing ratio of the non-addition-polymerizable free radical polymerizable monomer (B) contained in the addition-polymerizable raw material composition is not particularly limited, but is preferably 20 wt % to 80 wt %, more preferably 20 wt % to 50 wt % in terms of the polymerizable monomer mixing ratio Rp represented by the following formula (1').

[0140] Formula (1') Rp = 100 × Bp / [a1p + a2p + Bp]

[0141] In formula (1'), a1p represents the content (mass parts) of the free radical polymerizable diol compound (a1) contained in the addition polyreactive raw material composition, a2p represents the content (mass parts) of the diisocyanate compound (a2) contained in the addition polyreactive raw material composition, and Bp represents the content (mass parts) of the non-addition polymerizable free radical polymerizable monomer (B) contained in the addition polyreactive raw material composition.

[0142] By setting the polymerizable monomer mixing ratio Rp to 20wt% to 80wt%, not only can the operability of the addition polymerization reaction raw material composition be improved, but also the number average molecular weight of the radical polymerizable polyurethane component (A) generated by the addition polymerization reaction can be easily controlled within the range of 1500 to 5000. In addition, before and after the implementation of the addition polymerization reaction process, the total mass of the radical polymerizable diol compound (a1), the diisocyanate compound (a2) and the radical polymerizable polyurethane component (A) present in the reaction system does not change. Therefore, when using an addition polymerization reaction raw material composition with a polymerizable monomer mixing ratio Rp of 20wt% to 80wt%, it is extremely easy to prepare a radical polymerizable raw material composition with a polymerizable monomer mixing ratio Rr of 20wt% to 80wt%. This is because: when the composition after the addition polymerization reaction process is directly used as a radical polymerizable raw material composition, the polymerizable monomer mixing ratio Rp = polymerizable monomer mixing ratio Rr.

[0143] In addition, when the addition polymerization process is carried out using an addition polymerization reaction raw material composition having a polymerizable monomer mixing ratio Rp of less than 20 wt%, the polymerizable monomer mixing ratio Rr can be adjusted to be in the range of 20 wt% to 80 wt% after the addition polymerization process is completed. For example, when the addition polymerization process is carried out using an addition polymerization reaction raw material composition having a polymerizable monomer mixing ratio Rp of less than 20 wt%, the polymerizable monomer mixing ratio Rr can be adjusted to be 20 wt% or more by adding a non-addition polymerizable free radical polymerizable monomer (B) after the addition polymerization process is completed.

[0144] In addition, when the following conditions 1 and 2 are satisfied, it is preferred to adopt the (b) multi-step preparation method from the viewpoint of making it easier to ensure the uniformity of the obtained hardened body or to make it easier to ensure the operability of these raw material compositions during the preparation of the addition polymerization reactive raw material composition and the free radical polymerizable raw material composition.

[0145] <1> An addition-polymerizable raw material composition comprising at least a radically polymerizable diol compound (a1), a diisocyanate compound (a2), a non-addition-polymerizable radically polymerizable monomer (B), and a filler (D).

[0146] <2> A case where the filling rate of the filler (D) contained in the radical polymerizable raw material composition is high (for example, a case where the filling rate is about 60 wt % or more).

[0147] Hereinafter, as a modulation example of a polyaddition reactive raw material composition, an example of the steps of modulating a polyaddition reactive raw material composition by a multi-step modulation method is described. In this case, first, by mixing at least a free radical polymerizable diol compound (a1), a non-polyaddition free radical polymerizable monomer (B) and a filler (D), a primary raw material composition containing these substances is modulated. With respect to the primary raw material composition, all the components constituting the primary raw material composition can be mixed at once for modulation, or after a mixture of a part of the components constituting the primary raw material composition is modulated, the remaining components constituting the primary raw material composition are added and mixed for modulation. The content of each component in the primary raw material composition can be appropriately selected as follows: a polyaddition reactive raw material composition and a free radical polymerizable raw material composition having a target composition can be obtained. With respect to the modulation of the primary raw material composition, especially when the filling rate of the filler (D) in the manufactured hardened body is high, it is possible to more easily ensure the uniformity of the obtained hardened body, or further, when the polyaddition reactive raw material composition is in a paste state, a more outstanding operability can be obtained, which is very advantageous in these aspects.

[0148] When preparing the primary raw material composition, the mixing method for mixing the components is not particularly limited, and a method using an electromagnetic stirrer, an automatic mortar machine, a planetary mixer, a centrifugal mixer, etc. can be appropriately adopted. In addition, based on the reason that the filler (D) is easily dispersed uniformly, it is preferred that after preparing the mixed composition by first mixing the free radical polymerizable diol compound (a1) and the non-addition polymerizable free radical polymerizable monomer (B), the filler (D) is added to the mixed composition and mixed, thereby preparing the primary raw material composition. Furthermore, from the viewpoint of easy suppression of side reactions and easy dispersion, it is preferred to add the free radical polymerization initiator (C) to the primary raw material composition. Similarly, it is preferred to add other additives to the primary raw material composition. For the primary raw material composition thus prepared, it is preferred to perform a degassing treatment to eliminate the bubbles contained inside. As a degassing method, a known method can be used, and a method such as pressure degassing, vacuum degassing, centrifugal degassing, etc. can be arbitrarily used. In addition, by further adding or mixing the diisocyanate compound (a2) to the primary raw material composition, an addition polymerization reactive raw material composition can be prepared.

[0149] In addition, the addition-polymerizable raw material composition (the primary raw material composition when the addition-polymerizable raw material composition is prepared using the primary raw material composition) may further contain a catalyst for accelerating the addition reaction as other additives, if necessary, but may not contain a catalyst for accelerating the addition reaction. In addition, examples of catalysts for accelerating the addition reaction include tin octylate and dibutyltin diacetate.

[0150] (2) Polyaddition reaction

[0151] After the addition-polymerizable raw material composition is prepared, the radically polymerizable diol compound (a1) and the diisocyanate compound (a2) contained in the addition-polymerizable raw material composition are subjected to addition-polymerization reaction, thereby forming a radically polymerizable polyurethane component (A). The addition-polymerization reaction is started at the same time as the addition-polymerizable raw material composition is prepared, or it is started by heating the addition-polymerizable raw material composition as needed. The addition-polymerization reaction is carried out as follows: the addition-polymerization reaction is carried out until at least one of the radically polymerizable diol compound (a1) and the diisocyanate compound (a2) contained in the addition-polymerizable raw material composition is actually completely consumed by the addition-polymerization reaction, in other words, it is carried out until the degree of progress of the addition-polymerization reaction approaches the maximum value (saturation value). Therefore, when heating the addition-polymerizable raw material composition, the heating temperature and the heating time can be appropriately selected based on the above-mentioned points. In this case, the heating temperature is preferably 30°C to 100°C, and more preferably 35°C to 80°C. In addition, from the viewpoint that the degree of progress of the addition polymerization reaction can actually reach the vicinity of the maximum value (saturation value), the heating time is (1) preferably about 90 hours or more, more preferably about 100 hours or more, when the heating temperature is 30° C. or more and less than 35° C., (2) preferably about 65 hours or more, more preferably about 72 hours or more, and further preferably about 80 hours or more, when the heating temperature is 35° C. or more and less than 50° C., (3) preferably about 45 hours or more, more preferably about 55 hours or more, and further preferably about 65 hours or more, when the heating temperature is 50° C. or more and less than 75° C., (4) preferably about 24 hours or more, more preferably about 35 hours or more, and further preferably about 45 hours or more, when the heating temperature is 75° C. or more and 100° C. or less. In the cases shown in (1) to (4) above, the upper limit of the heating time is not particularly limited, but is preferably 168 hours or less from the practical viewpoint of production efficiency and the like.

[0152] In addition, when the addition polymerization reaction includes a free radical polymerization initiator (C) to the raw material combination group, a method is adopted in which a free radical polymerization reaction does not actually occur during the addition polymerization reaction (however, in the method for producing the polyurethane composite material of the present embodiment, a free radical polymerization reaction that is inevitably generated in a small amount is allowed even if this method is adopted). When the free radical polymerization reaction also significantly occurs during the addition polymerization reaction, the free radical polymerization process actually starts before the addition polymerization reaction process and the free radical polymerizable raw material composition preparation process are completed, so the implementation of the method for producing the polyurethane composite material of the present embodiment itself becomes impossible. However, by adopting the above method, even in the case where the addition polymerization reaction raw material composition includes a free radical polymerization initiator (C), the free radical polymerization process can be implemented after the addition polymerization reaction process and the free radical polymerizable raw material composition preparation process are completed.

[0153] There are no particular restrictions on the method for preventing a free radical polymerization reaction from actually occurring during the addition polymerization reaction. For example, the methods shown in the following (1) and (2) can be suitably adopted. That is, (1) when a photopolymerization initiator is used as the free radical polymerization initiator (C), it is preferred to prepare the addition polymerization reaction raw material composition or carry out the addition polymerization reaction in an environment where light having a wavelength that activates the photopolymerization initiator (activating light) is not irradiated. In addition, (2) when a thermal polymerization initiator is used as the free radical polymerization initiator (C), it is preferred to prepare the addition polymerization reaction raw material composition while maintaining the temperature at 80°C to 20°C lower than the 10-hour half-life temperature of the thermal polymerization initiator, and it is more preferred to prepare the addition polymerization reaction raw material composition while maintaining the temperature at 70°C to 50°C lower than the 10-hour half-life temperature of the thermal polymerization initiator.

[0154] In addition, when the addition polymerization reactive raw material composition is produced by a multi-step modulation method, the method shown in (1) above is also applicable to a raw material composition containing a photopolymerization initiator used in the multi-step modulation method to modulate the addition polymerization reactive raw material composition (for example, a primary raw material composition also containing a photopolymerization initiator, etc.), and the method shown in (2) above is also applicable to a raw material composition containing a thermal polymerization initiator used in the multi-step modulation method to modulate the addition polymerization reactive raw material composition (for example, a primary raw material composition also containing a thermal polymerization initiator, etc.).

[0155] In addition, when modulating the addition polyreactive raw material composition and the raw material composition (primary raw material composition etc.) utilized as required for the modulation addition polyreactive raw material composition, the mixing method for mixing each component is not particularly limited, and known mixing methods can be appropriately utilized. As such mixing method, for example, the method using electromagnetic stirrer, automatic mortar machine, planetary mixer, centrifugal mixer etc. can be enumerated. In addition, in order to prevent bubbles from being mixed in the composition being mixed, it is also possible to mix under pressurized conditions and / or vacuum conditions.

[0156] 3-2. Radical polymerizable raw material composition preparation step

[0157] (1) Step of preparing the radical polymerizable raw material composition

[0158] In the radical polymerizable raw material composition preparation step, a radical polymerizable raw material composition containing a radical polymerizable polyurethane component (A), a non-addition polymerizable radical polymerizable monomer (B), a radical polymerization initiator (C), and a filler (D) is prepared.

[0159] The preparation step of the radical polymerizable raw material composition is appropriately determined according to the composition of the addition polymerization reactive raw material composition. In this case, the preparation step can be described separately for the case where the addition polymerization reactive raw material composition contains the components listed in <1>, the case where the components listed in <2>, the case where the components listed in <3>, and the case where the components listed in <4>, wherein the components listed in <1>, <2>, <3>, and <4> are components of the five components (radical polymerizable diol compound (a1), diisocyanate compound (a2), non-addition polymerizable radical polymerizable monomer (B), radical polymerization initiator (C), and filler (D)) corresponding to the four essential components (radical polymerizable polyurethane component (A), non-addition polymerizable radical polymerizable monomer (B), radical polymerization initiator (C), and filler (D)) contained in the radical polymerizable raw material composition.

[0160] <1> A radically polymerizable diol compound (a1), a diisocyanate compound (a2), a non-addition polymerizable radically polymerizable monomer (B), and a radical polymerization initiator (C).

[0161] <2> A radically polymerizable diol compound (a1), a diisocyanate compound (a2), a non-addition polymerizable radically polymerizable monomer (B), and a filler (D).

[0162] <3> A radically polymerizable diol compound (a1), a diisocyanate compound (a2), a non-addition-polymerizable radically polymerizable monomer (B), a radical polymerization initiator (C), and a filler (D).

[0163] <4> A radically polymerizable diol compound (a1), a diisocyanate compound (a2), and a non-addition polymerizable radically polymerizable monomer (B).

[0164] <First Preparation Step>

[0165] When the addition-polymerizable raw material composition includes the components listed in <1> above, first, in the addition-polymerizable raw material composition, a radically polymerizable polyurethane component (A) is formed by allowing a radically polymerizable diol compound (a1) and a diisocyanate compound (a2) to undergo addition polymerization, and the addition polymerization step is terminated. Then, the radically polymerizable raw material composition can be prepared by adding or mixing a filler (D) to an intermediate composition including the radically polymerizable polyurethane component (A), a non-additionally polymerizable radically polymerizable monomer (B) and a radical polymerization initiator (C). It should be noted that in the first preparation step, the addition polymerization step and the radically polymerizable raw material composition preparation step are carried out in sequence.

[0166] <Second Preparation Step>

[0167] When the addition-polymerizable raw material composition contains the components listed in <2> above, first, in the addition-polymerizable raw material composition, the radically polymerizable diol compound (a1) and the diisocyanate compound (a2) are subjected to addition polymerization to form a radically polymerizable polyurethane component (A), and the addition polymerization step is terminated. Then, a radical polymerization initiator (C) is added or mixed to an intermediate composition containing the radically polymerizable polyurethane component (A), the non-addition-polymerizable radically polymerizable monomer (B) and the filler (D), thereby preparing the radically polymerizable raw material composition.

[0168] It should be noted that, in the second preparation step, the addition polymerization step and the radical polymerizable raw material composition preparation step are also carried out in sequence. In addition, in the second preparation step, the radical polymerization initiator (C) is added or mixed with the intermediate composition obtained through the addition polymerization step. Therefore, it is not necessary to adopt the method in which the radical polymerization reaction does not actually occur during the addition polymerization reaction as exemplified in the above (1) and (2).

[0169] <Third Preparation Step>

[0170] When the addition-polymerizable raw material composition contains the components listed in <3> above, first, in the addition-polymerizable raw material composition, the radically polymerizable diol compound (a1) and the diisocyanate compound (a2) are subjected to addition polymerization to form the radically polymerizable polyurethane component (A), and the addition polymerization step is completed. In addition, by completing the addition polymerization step, the preparation of the radically polymerizable raw material composition containing all four essential components is also completed. That is, in the third preparation step, the addition polymerization step is completed and the preparation step of the radically polymerizable raw material composition is also completed.

[0171] <Fourth modulation step>

[0172] When the addition-polymerizable raw material composition includes the components listed in <4> above, first, in the addition-polymerizable raw material composition, a radically polymerizable polyurethane component (A) is formed by allowing a radically polymerizable diol compound (a1) and a diisocyanate compound (a2) to undergo an addition-polymerization reaction, and the addition-polymerization step is terminated. Then, a radical polymerization initiator (C) and a filler (D) are added or mixed to an intermediate composition including the radically polymerizable polyurethane component (A) and a non-additionally polymerizable radically polymerizable monomer (B), thereby modulating the radically polymerizable raw material composition. It should be noted that in the fourth modulation step, the addition-polymerization step and the radically polymerizable raw material composition modulation step are sequentially performed.

[0173] (2) Phase morphology of radical polymerizable raw material composition

[0174] Among the four essential components constituting the free radical polymerizable raw material composition, the components that are the main components in terms of content are the free radical polymerizable polyurethane component (A), the non-addition polymerizable free radical polymerizable monomer (B) and the filler (D). Here, the non-addition polymerizable free radical polymerizable monomer (B) is a low molecular weight substance that is liquid at room temperature. Moreover, although the free radical polymerizable polyurethane component (A) is a high molecular weight substance, its number average molecular weight is a relatively small value of 1500 to 5000 (that is, the molecular size is quite small). Therefore, the free radical polymerizable polyurethane component (A) will not precipitate in the non-addition polymerizable free radical polymerizable monomer (B) and is easily dissolved. Therefore, as long as the filling rate of the filler (D) is not too large, the free radical polymerizable raw material composition used in the method for producing the polyurethane composite material of this embodiment usually exists as a paste-like composition. In addition, when the phase form of the radical polymerizable raw material composition is a paste, a radical polymerizable raw material composition having a polymerizable monomer mixing ratio Rr of 20 wt% to 80 wt%, in other words, a radical polymerizable raw material composition containing a sufficient amount of low molecular weight components (non-addition polymerizable radical polymerizable monomer (B)) also has excellent handleability. In addition, from the viewpoint of making the phase form of the radical polymerizable raw material composition more reliably a paste, the filling rate of the filler (D) is usually preferably 85 wt% or less, and more preferably 80 wt% or less.

[0175] In addition, as long as the radical polymerization initiator (C) is not activated by light irradiation and / or heat treatment, the radical polymerizable raw material composition is a composition that is extremely stable at a temperature near room temperature. Therefore, the viscosity of the paste-like radical polymerizable raw material composition remains constant over time. Therefore, as long as the radical polymerization initiator (C) is not activated under a room temperature environment, the paste-like radical polymerizable raw material composition can continue to maintain excellent operability for a very long time from shortly after it is prepared.

[0176] Therefore, when the free radical polymerizable raw material composition is a paste-like raw material composition, a free radical polymerization process (hardening process) can also be implemented after the free radical polymerizable raw material composition is injected into the mold frame. In this case, a hardened body having a desired size and shape corresponding to the mold frame can be obtained. In addition, the hardening of the free radical polymerizable raw material composition after being injected into the mold frame is only due to free radical polymerization. Therefore, compared with the technology disclosed in Patent Document 3 that forms a hardened body through a process in which addition polymerization and free radical polymerization are carried out simultaneously and in parallel in the raw material composition after being injected into the mold frame, when the mold is formed by the manufacturing method of the polyurethane composite material of the present embodiment using the paste-like free radical polymerizable raw material composition, the polymerization shrinkage during hardening can be suppressed, and as a result, a hardened body with a small deviation from the size and shape of the mold frame and high dimensional shape accuracy can be easily obtained. In addition, when the mold is formed using the mold frame, usually, at least a thermal polymerization initiator is mixed as a free radical polymerization initiator (C) in the paste-like free radical polymerizable raw material composition, and the free radical polymerization process is implemented by at least heating.

[0177] 3-3. Radical polymerization step (hardening step)

[0178] The free radical polymerization step (hardening step) is implemented after the addition polymerization step and the free radical polymerizable raw material composition modulation step are completed. In the free radical polymerization step, free radical polymerization is carried out by activating the free radical polymerization initiator (C) contained in the free radical polymerizable raw material composition, so that the free radical polymerizable raw material composition is hardened. Thus, a hardened body composed of a polyurethane composite material is obtained. When a thermal free radical polymerization initiator is used as the free radical polymerization initiator (C), free radical polymerization is carried out by heating the free radical polymerizable raw material composition, and when a light free radical polymerization initiator is used as the free radical polymerization initiator (C), free radical polymerization is carried out by irradiating the free radical polymerizable raw material composition with light that activates it.

[0179] Since free radical polymerization generates heat due to reaction heat, it is preferable to control the heating temperature (hardening temperature) during heating when a thermal free radical polymerization initiator is used as the free radical polymerization initiator (C). In this case, it is preferable to control the heating temperature to not more than 150°C, and it is particularly preferable to heat within a temperature range of -10°C to +25°C of the 10-hour half-life temperature of the thermal free radical polymerization initiator, that is, when the 10-hour half-life temperature is set to T (°C), heating is performed within a range of a temperature (lower limit temperature L) 10°C lower than the 10-hour half-life temperature T to a temperature (upper limit temperature H) 25°C higher than the 10-hour half-life temperature T. By setting the heating temperature to be above the lower limit temperature L, not only can the free radical polymerization rate be sufficiently fast, but also the hardened body can be easily prevented from being unintentionally colored. In addition, by setting the heating temperature to be below the upper limit temperature H, it is possible to prevent excessive consumption of free radical polymerizable groups present in the reaction system, and it is also possible to suppress the rapid progress of free radical polymerization. By controlling the heating temperature within the above-mentioned temperature range, the polymerization hardening is carried out at an industrially acceptable reaction rate, and it is also possible to suppress the formation of skewness or cracks in the hardened body due to the rapid reaction. Furthermore, it is also possible to easily suppress the degradation of the non-addition polymerizable free radical polymerizable monomer (B). In addition, when free radical polymerization is carried out by heating, in order to suppress the formation of voids (voids) from bubbles in the hardened body, the free radical polymerizable raw material composition in the free radical polymerization can be pressurized. The method of pressurization is not limited, and it can be pressurized mechanically or by gas such as nitrogen.

[0180] By carrying out the radical polymerization step in this manner, a polyurethane composite material in which the filler (D) is dispersed in the polyurethane resin matrix can be obtained.

[0181] Regarding the free radical polymerization reaction, by appropriately controlling the free radical polymerization conditions, the reaction can be carried out until the unreacted free radical polymerizable groups present in the free radical polymerizable raw material composition are actually completely consumed, or the reaction can be terminated in a state where a certain amount of unreacted free radical polymerizable groups remain in the hardened body. For example, when a thermal polymerization initiator is used as the free radical polymerization initiator (C), the degree of progress of the free radical polymerization reaction at the end point of the free radical polymerization reaction (the residual rate of free radical polymerizable groups) can be controlled by controlling the heating temperature or the heating time. However, in the method for manufacturing the polyurethane composite material of the present embodiment, from the viewpoint of more reliably obtaining a hardened body with excellent strength, the residual rate of free radical polymerizable groups is controlled not to be too large. Specifically, the residual rate of free radical polymerizable groups is particularly preferably controlled to be within the range of 0% to 25%. It should be noted that when the residual rate of free radical polymerizable groups is controlled to be 10% to 25%, a hardened body with excellent strength, water resistance, uniformity and adhesion can be obtained. On the other hand, when the residual radical polymerizable group ratio is controlled to be 0% or more and less than 10%, a cured product with relatively reduced or no adhesiveness but better strength can be obtained compared to when the residual radical polymerizable group ratio is controlled to be 10% to 25%.

[0182] In order to control the residual rate of radical polymerizable groups within the range of 10% to 25%, it is preferred that the heating temperature and the heating time be set within the ranges shown in the following (a1) and (b1).

[0183] (a1) Heating temperature: -10°C to +25°C, which is the 10-hour half-life temperature of the thermal radical polymerization initiator used as the radical polymerization initiator (C).

[0184] (b1) Heating time: 2 hours to 120 hours

[0185] In addition, from the perspective of controlling the residual rate of free radical polymerizable groups within the range of 10% to 25% and more reliably preventing coloration or modification of the polyurethane composite material, the heating temperature and heating time are more preferably set within the ranges shown below (a2) and (b2), and further preferably set within the ranges shown below (a3) ​​and (b3).

[0186] (a2) Heating temperature: in the range of +0°C to +25°C of the 10-hour half-life temperature of the thermal radical polymerization initiator used as the radical polymerization initiator (C)

[0187] (b2) Heating time: 5 hours to 72 hours

[0188] (a3) Heating temperature: in the range of +10°C to +25°C of the 10-hour half-life temperature of the thermal radical polymerization initiator used as the radical polymerization initiator (C)

[0189] (b3) Heating time: 8 hours to 24 hours

[0190] On the other hand, when the residual radical polymerizable group ratio is controlled within a range of less than 10%, it is preferred to select a relatively higher heating temperature and / or a longer heating time than when the ratio is controlled within a range of 10% to 25%.

[0191] In addition, the above-mentioned adhesiveness refers to the property of the unreacted free radical polymerizable groups remaining in the polyurethane composite material and not participating in the free radical polymerization, that is, it refers to the improvement of adhesive strength and adhesive durability. There is no particular limitation on the use form of the polyurethane composite material that can exert such excellent adhesiveness, for example, the case where the polyurethane composite material having a free radical polymerizable group residual rate of 10% to 25% and other materials are bonded using an adhesive containing a free radical polymerizable monomer.

[0192] The residual rate of free radical polymerizable groups can be calculated from the peak area at a specific wavelength obtained by measuring the free radical polymerizable raw material composition before the start of free radical polymerization and the hardened body (polyurethane composite material) obtained after the free radical polymerization of the free radical polymerizable raw material composition using Fourier transform infrared spectroscopy (FT-IR). In this case, the residual rate of free radical polymerizable groups is calculated according to the following formula (3).

[0193] Formula (3) Residual rate of free radical polymerizable groups (%) = (r1 / r0) × 100

[0194] In formula (3), r0 represents the normalized peak area ratio (ν6170 / ν4920) obtained by normalizing the two peak areas (ν6170 and ν4920) obtained by FT-IR measurement of the free radical polymerizable raw material composition before the start of free radical polymerization, and dividing the peak area (ν6170) by the peak area (ν4920); r1 represents the normalized peak area ratio (ν6170 / ν4920) obtained by normalizing the two peak areas (ν6170 and ν4920) obtained by FT-IR measurement of the hardened body (polyurethane composite material) obtained after the completion of free radical polymerization, and dividing the peak area (ν6170) by the peak area (ν4920).

[0195] Here, the peak area (ν6170) represents 6170 cm of carbon-carbon double bonds derived from free radical polymerizable groups. -1 The peak area of ​​the absorption peak observed near the peak area (ν4920) indicates that the carbonyl group derived from the carbamate bond is 4920 cm -1 The peak area of ​​the absorption peak observed near .

[0196] 4. Application example of the method for producing polyurethane composite materials (production of dental cutting materials)

[0197] When the free radical polymerizable raw material composition used in the manufacturing method of the polyurethane composite material of the present embodiment is a pasty composition, the free radical polymerization process (hardening process) can also be implemented after the free radical polymerizable raw material composition is injected into the mold frame as described above. In addition, the obtained hardened body (polyurethane composite material) also maintains high strength and has water resistance in the hydrophilic environment of the inside of the oral cavity. Due to such high water resistance, the manufacturing method of the polyurethane composite material of the present embodiment can be suitably used as the manufacturing method of the dental cutting material, especially when the dental cutting material is cut and processed by using the dental CAD / CAM system to manufacture the dental prosthesis. Below, about the manufacturing method of the polyurethane composite material of the present embodiment, the suitable specific example when being used for the manufacture of the dental cutting material is described.

[0198] First, similarly to the method for manufacturing the polyurethane composite material of the present embodiment, a pasty free radical polymerizable raw material composition is prepared. Then, after the free radical polymerizable raw material composition is injected into the mold frame, it is heated to implement the free radical polymerization process (hardening process). The mold frame used in the mold forming is not particularly limited, and according to the shape pre-conceived for each product form, a prism-shaped, cylindrical, square plate-shaped, or disc-shaped mold frame is appropriately used. In addition, regarding the size and shape of the mold frame, considering the shrinkage rate during free radical polymerization, etc., it can be formed into a size and shape that is roughly consistent with the size and shape of the hardened body after free radical polymerization, or, when the hardened body obtained by free radical polymerization is processed in the later process, it can be formed into a size and shape slightly larger than the size and shape of the hardened body obtained after estimating the processing allowance.

[0199] About the injection method of the free radical polymerizable raw material composition of pasty state injected into the mold frame, there is no particular limitation, and known methods can be utilized. But preferably adopt pressure casting or vacuum casting. By adopting this injection method, it is possible to suppress the formation of bubbles mixed in the obtained hardened body (polyurethane composite material) or the cavity, as a result, it is possible to obtain the dental cutting material with excellent intensity and aesthetics. In addition, when it is pressure casting, the method of pressurization is not limited, and mechanical pressurization can be utilized, and gas pressurization of nitrogen etc. can also be utilized.

[0200] After the obtained hardened body is taken out from the mold frame, it is subjected to post-processing or post-processing such as heat treatment for relieving residual stress, shape correction by cutting, grinding, etc. as needed. Then, the hardened body subjected to these post-processing or post-processing is further joined with a fixing member such as a pin for holding it on a CAD / CAM device, thereby obtaining a dental cutting material.

[0201] 5. Polyurethane composite materials and dental cutting materials

[0202] As the polyurethane composite material manufactured by the manufacturing method of the polyurethane composite material of the present embodiment, it is preferred that the polyurethane composite material is manufactured by further satisfying the manufacturing conditions shown in the following (a) to (c) in the manufacturing method of the polyurethane composite material of the present embodiment. In this case, a hardened body (the first polyurethane composite material of the present embodiment) having a content of filler (D) corresponding to the manufacturing conditions shown in the following (a) and a residual rate of free radical polymerizable groups shown in the following (d) can be obtained. In addition, the residual rate of free radical polymerizable groups shown in the following (d) is more preferably 10% to 20%.

[0203] (a) The content of the filler (D) in the radical polymerizable raw material composition is 60 wt % to 85 wt %.

[0204] (b) A thermal radical polymerization initiator is used as the radical polymerization initiator (C).

[0205] (c) The radical polymerization step is carried out in a state where the mixture is heated to a temperature of -10°C to +25°C, which is the 10-hour half-life temperature of the thermal radical polymerization initiator.

[0206] (d) In the copolymer of the radically polymerizable polyurethane component (A) and the non-additionally polymerizable free radically polymerizable monomer (B) formed in the free radical polymerization step, 10% to 25% of the total amount of free radically polymerizable groups possessed by the radically polymerizable diol compound (a1) and the non-additionally polymerizable free radically polymerizable monomer (B) contained in the radically polymerizable raw material composition remains (i.e., the residual free radically polymerizable group rate is 10% to 25%).

[0207] The first embodiment of the polyurethane composite material is a composite material manufactured by the manufacturing method of the polyurethane composite material of the present embodiment, and therefore, it not only has excellent strength, water resistance, and uniformity, but also has a free radical polymerizable group residual rate of 10% to 25%, and therefore also has excellent adhesion.

[0208] In addition, the polyurethane composite material of the second embodiment is composed of a composite material including a polyurethane resin matrix and a filler dispersed in the polyurethane resin matrix, wherein the polyurethane resin matrix is ​​composed of a copolymer of a polyurethane having a number average molecular weight of 1500 to 5000 and having a free radical polymerizable group and a free radical polymerizable monomer that does not undergo addition polymerization with a hydroxyl group and an isocyanate group, wherein the content of free radical polymerizable carbon-carbon double bonds contained in 1 g of the polyurethane resin matrix is ​​0.5 mmol / g to 1.0 mmol / g, and the content of the filler in the composite material is 60 wt% to 85 wt%. It should be noted that the "free radical polymerizable monomer that does not undergo addition polymerization with a hydroxyl group and an isocyanate group" refers to a compound having the same molecular structure as the above-mentioned non-addition polymerizable free radical polymerizable monomer (B).

[0209] The polyurethane composite material of the second embodiment is a composite material determined from different observation points of the polyurethane composite material of the first embodiment based on the experimental data described later. Therefore, the polyurethane composite material of the second embodiment is not only excellent in strength, water resistance, and uniformity, but also has more excellent adhesion.

[0210] The content of radically polymerizable carbon-carbon double bonds per 1 g of the polyurethane-based resin matrix (hereinafter, sometimes referred to as double bond content) is preferably 0.7 mmol / g to 1.0 mmol / g.

[0211] The amount of double bonds (mmol / g) in the polyurethane composite material of the second embodiment refers to a value determined by converting the value of the peak area (ν6170) into the amount of double bonds using a pre-made calibration curve, wherein the value of the peak area (ν6170) is obtained by performing FT-IR measurement on a measurement sample that is the subject of the investigation of the amount of double bonds. However, in the case where the measurement sample that is the subject of the investigation of the amount of double bonds is manufactured by the method for manufacturing the polyurethane composite material of the present embodiment and its manufacturing conditions are known, the amount of double bonds (mmol / g) in the polyurethane composite material of the second embodiment can be obtained as the amount of double bonds in the measurement sample by the theoretical amount of double bonds calculated based on the formula (4) described later.

[0212] Here, the calibration curve is made according to the following steps. First, using the manufacturing method of the polyurethane composite material of the present embodiment, a plurality of calibration curve making samples manufactured according to various manufacturing conditions are prepared. Here, for each calibration curve making sample, the value of the free radical polymerizable group residual rate shown in formula (3) is also calculated and obtained. Then, for each calibration curve making sample, the theoretical double bond amount (theoretical double bond amount) is calculated according to formula (4) described later. In addition, by implementing FT-IR measurement on each calibration curve making sample, the peak area (ν6170) is measured. Then, by using the X-axis as the measured value of the peak area (ν6170) obtained by FT-IR measurement and the Y-axis as the theoretical double bond amount (mmol / g) on ​​a chart, the value obtained for each calibration curve making sample is illustrated to obtain a calibration curve. In addition, the FT-IR measurement conditions of the measuring sample and the FT-IR measurement conditions of the calibration curve making sample are substantially the same.

[0213] Formula (4) Theoretical double bond amount = initial double bond amount × residual rate of free radical polymerizable groups / 100

[0214] In formula (4), the initial double bond amount refers to the total amount (mmol / g) of unreacted radical polymerizable groups in the raw material composition (addition polymerization reaction raw material composition used in the preparation of the radical polymerizable raw material composition) before the start of radical polymerization when preparing the sample for the calibration curve determined based on the following formula (5), and the residual rate of radical polymerizable groups refers to the residual rate (%) of radical polymerizable groups determined according to formula (3).

[0215] [Formula 2]

[0216] Formula (5)

[0217] In formula (5), p represents an integer greater than 1 and is the number of types of free radical polymerizable diol compounds (a1) contained in the addition polymerization reaction raw material composition used in the addition polymerization reaction step, a represents an integer from 1 to p, q represents an integer greater than 1 and is the number of types of non-addition polymerizable free radical polymerizable monomers (B) contained in the addition polymerization reaction raw material composition used in the addition polymerization reaction step, and b represents an integer from 1 to q.

[0218] In addition, Xa represents the content (mmol) of the ath free radical polymerizable diol compound (a1) contained in the addition polymerization reaction raw material composition used in the addition polymerization reaction step, αa represents the number of free radical polymerizable groups contained in each molecule of the ath free radical polymerizable diol compound (a1), Yb represents the content (mmol) of the bth non-addition polymerizable free radical polymerizable monomer (B) contained in the addition polymerization reaction raw material composition used in the addition polymerization reaction step, and βb represents the number of free radical polymerizable groups contained in each molecule of the bth non-addition polymerizable free radical polymerizable monomer (B).

[0219] Furthermore, M represents the mass (g) of the polyaddition reactive raw material composition used in the polyaddition reaction step. However, when the polyaddition reactive raw material composition used in the polyaddition reaction step further contains an insoluble component (e.g., filler (D)) that is insoluble in any one of the radically polymerizable diol compound (a1), the diisocyanate compound (a2), and the non-additionally polymerizable radically polymerizable monomer (B), M represents the mass (g) obtained by excluding the mass (g) of the insoluble component contained in the polyaddition reactive raw material composition from the mass (g) of the polyaddition reactive raw material composition.

[0220] As described above, the polyurethane composite materials of the first and second embodiments are excellent in strength, water resistance, and uniformity, and also excellent in adhesion, and therefore can be widely used in various applications. In particular, as a suitable application that can effectively utilize these four characteristics, for example, a dental cutting material used in a dental CAD / CAM system can be cited. When a dental prosthesis is manufactured using a dental CAD / CAM system using the dental cutting material composed of the polyurethane composite materials of the first and second embodiments, the obtained dental prosthesis has excellent strength, water resistance, and aesthetics, and also has better adhesion to dentin and adhesion durability.

[0221] 6. Polyurethane resin materials

[0222] In addition, the polyurethane composite materials of the first and second embodiments contain filler (D) as an essential component, but can also be used in a form without filler (D) as an essential component. As suitable polyurethane resin materials based on this form, the polyurethane resin materials of the first and second reference embodiments described below can be cited.

[0223] That is, the polyurethane-based resin material according to the first reference embodiment is preferably as follows.

[0224] The method comprises the steps of: a polyaddition reaction step, a radical polymerizable raw material composition preparation step, and a radical polymerization step, wherein in the polyaddition reaction step, in a polyaddition reaction raw material composition comprising a diol compound (a1) having one or more radical polymerizable groups, a diisocyanate compound (a2), and a polymerizable monomer (B) having one or more radical polymerizable groups in its molecule and not undergoing a polyaddition reaction with the diol compound (a1) and the diisocyanate compound (a2), a polyaddition reaction is performed with the diol compound (a1) and the diisocyanate compound (a2) to form a polyurethane component (A) having a number average molecular weight of 1500 to 5000 and having a radical polymerizable group, and in the radical polymerizable raw material composition preparation step, a polyurethane component (A) comprising the polyurethane component (A), the polymerizable monomer (B), and a radical polymerization initiator (C) is prepared. A polyurethane resin material is formed by free radical polymerization using a radical polymerizable raw material composition in a free radical polymerization step after the addition reaction step and the free radical polymerizable raw material composition modulation step are completed; the polymerizable monomer mixing ratio Rr represented by the following formula (1) is 20wt% to 80wt%, a thermal free radical inactive initiator is used as a free radical polymerization initiator (C), and the free radical polymerization step is carried out in a state where the material is heated to a temperature of -10°C to +25°C which is the 10-hour half-life temperature of the thermal free radical polymerization initiator; and in the copolymer of the polyurethane component (A) and the polymerizable monomer (B) formed in the free radical polymerization step, 10% to 25% of the total amount of free radical polymerizable groups possessed by the diol compound (a1) and the polymerizable monomer (B) contained in the free radical polymerizable raw material composition remain.

[0225] Formula (1) Rr=100×Br / [a1r+a2r+Ar+Br]

[0226] In formula (1), a1r represents the content (parts by mass) of the unreacted diol compound (a1) remaining in the free radical polymerizable raw material composition, a2r represents the content (parts by mass) of the unreacted diisocyanate compound (a2) remaining in the free radical polymerizable raw material composition, Ar represents the content (parts by mass) of the polyurethane component (A) contained in the free radical polymerizable raw material composition, and Br represents the content (parts by mass) of the polymerizable monomer (B) contained in the free radical polymerizable raw material composition.

[0227] In addition, the polyurethane-based resin material of the second reference embodiment is preferably as follows.

[0228] The polyurethane resin material at least comprises a copolymer of a polyurethane having a number average molecular weight of 1500 to 5000 and having a free radical polymerizable group and a free radical polymerizable monomer that does not undergo additional reaction with a hydroxyl group and an isocyanate group. The content of free radical polymerizable carbon-carbon double bonds contained in each 1g of the polyurethane resin matrix composed of the copolymer is 0.5mmol / g to 1.0mmol / g.

[0229] The polyurethane resin materials of the first and second reference embodiments may (i) contain 60 wt% to 85 wt% of filler (D) as required, similar to the polyurethane composite materials of the first and second present embodiments, (ii) may contain more than 0 wt% and less than 60 wt%, or more than 85 wt% and less than 100 wt% of filler (D), or (iii) may not contain filler (D) at all. In addition, the polyurethane resin materials of the first and second reference embodiments may contain one or more additives selected from various additives such as filler (D), fluorescent agent, ultraviolet absorber, antioxidant, pigment, antibacterial material, X-ray contrast agent, etc. as required.

[0230] [Example]

[0231] Hereinafter, the present invention will be described with reference to Examples and Comparative Examples; however, the present invention is not limited to these Examples.

[0232] 1.Raw materials

[0233] Hereinafter, each component used in each Example and Comparative Example and its abbreviation are shown.

[0234] (1) Radically polymerizable diol compound (a1)

[0235] GLM: glycerol monomethacrylate (OH distance: 2)

[0236] bis-GMA: Bisphenol A diglycidylmethacrylate (OH distance: 19)

[0237] (2) Non-radical polymerizable polyol compounds

[0238] PG:propylene glycol

[0239] GTP: glycerol tripropoxylate (average molecular weight = 266)

[0240] (3) Diisocyanate compound (a2)

[0241] XDI: m-xylene diisocyanate

[0242] (4) Non-addition polymerizable free radical polymerizable monomer (B)

[0243] 1G: ethylene glycol dimethacrylate

[0244] 2G: diethylene glycol dimethacrylate

[0245] 3G: triethylene glycol dimethacrylate

[0246] 9G: polyethylene glycol #400 dimethacrylate

[0247] A-TMPT-3EO: EO modified trimethylolpropane triacrylate (Trimethylolpropanetriacrylate-3EO)

[0248] A-DOG: Dioxane glycol Diacrylate

[0249] UDMA: 1,6-bis(methacrylethyloxycarbonylamino)-2,2,4-trimethylhexane

[0250] (5) Radical polymerization initiator (C)

[0251] PBL: tert-butylperoxylaurate (10-hour half-life temperature 98°C)

[0252] V-65: 2,2'-Azobis(2,4-dimethylvaleronitrile) (10-hour half-life temperature 51°C)

[0253] BPO: benzoyl peroxide (10-hour half-life temperature 74°C)

[0254] (6) Filler (D)

[0255] F1: Silica-zirconia (average particle size: 0.4 μm, surface treated with methacrylic acid 3-(trimethoxysilyl)propyl)

[0256] F2: Silica-titania (average particle size: 0.08 μm, surface treated with 3-(trimethoxysilyl)propyl methacrylate)

[0257] 2. Method for manufacturing polyurethane composite materials

[0258] Hereinafter, examples and comparative examples of the method for producing the polyurethane composite material of the present invention will be shown together.

[0259] (Example A1)

[0260] (1) Primary Raw Material Composition Preparation Step

[0261] First, a mixed composition was prepared by mixing 10.63 parts by mass of GLM as a radical polymerizable diol compound (a1), 5.79 parts by mass of 1G as a non-addition polymerizable radical polymerizable monomer (B), and 0.08 parts by mass of PBL as a radical polymerization initiator (C). Next, 49.70 parts by mass of F1 and 21.30 parts by mass of F2 as fillers (D) were added to the mixed composition and mixed to prepare a primary raw material composition.

[0262] (2) Polyaddition Reaction Step and Radical Polymerizable Raw Material Composition Preparation Step

[0263] By adding 12.50 parts by mass of XDI as a diisocyanate compound (a2) into a rotary and revolving agitator containing the entire amount of the obtained primary raw material composition and mixing, an addition-polymerizable raw material composition is prepared. Next, the obtained addition-polymerizable raw material composition is allowed to stand in a thermostat at 37° C. for 168 hours to perform an addition-polymerization reaction to form a radically polymerizable polyurethane component (A), thereby preparing a radically polymerizable raw material composition. It should be noted that the heating conditions (37° C., 168 hours) during the addition-polymerization reaction are conditions that allow the degree of progress of the addition-polymerization reaction to reach a maximum value (saturation value).

[0264] Here, in this embodiment, the molar ratio of the diisocyanate compound (a2) to the radical polymerizable diol compound (a1) immediately after the addition polymerization reaction raw material composition is prepared (hereinafter, sometimes referred to as "a2 / a1 molar ratio") is 1.0. In addition, the polymerizable monomer mixing ratio Rr is 20wt%. Furthermore, the ratio of the mass of the filler (D) to the mass of the radical polymerizable raw material composition (filling rate) is 71wt%. In addition, except for the case where the mixture is heated to 37°C during the addition polymerization reaction, the preparation of each composition is carried out under normal temperature (25°C).

[0265] In addition, in this example, the composition obtained by performing the addition polymerization step is directly used as a free radical polymerizable raw material composition. In addition, in this case, as described above, the relationship of the polymerizable monomer mixing ratio Rp shown in formula (1') = the polymerizable monomer mixing ratio Rr shown in formula (1) is established. Therefore, the polymerizable monomer mixing ratio Rr shown in Table 1 is calculated using formula (1').

[0266] (3) Evaluation of Radically Polymerizable Raw Material Composition

[0267] (3-1) Measurement of number average molecular weight of polyurethane component (A) (GPC measurement)

[0268] 1 g of the obtained free radical polymerizable raw material composition was weighed into a screw-capped tube bottle, and 3.5 ml of THF was added and stirred to obtain a THF solution, which was centrifuged at 10000 rpm for 10 minutes using a centrifuge (manufactured by AS ONE Co., Ltd.). Next, the supernatant obtained by centrifugation was filtered using a membrane filter (pore size 20 μm, manufactured by ADVANTEC (brand name) Toyo Co., Ltd.) to obtain a filtrate. Then, the filtrate was subjected to GPC measurement under the GPC measurement conditions shown below to obtain the number average molecular weight of the free radical polymerizable polyurethane component (A) obtained by the addition polymerization reaction in terms of polystyrene. As a result, the number average molecular weight was 3500.

[0269] [GPC measurement conditions]

[0270] Measuring device: Advanced Polymer Chromatography (manufactured by Waters Japan)

[0271]

[0272] Column temperature: 40°C

[0273] Developing solvent: THF (flow rate: 0.5 ml / min)

[0274] Detector: Photodiode array detector 254nm (PDA detector)

[0275] (3-2) Operational evaluation

[0276] The operability of the radical polymerizable raw material composition was evaluated by measuring the maximum load when a 5mm diameter stainless steel (SUS) round rod was pressed into a specified depth at a specified speed. The maximum load was measured according to the following steps. First, the radical polymerizable raw material composition was filled into a SUS nut-shaped mold and its surface was flattened, and placed under light-shielding conditions for 2 minutes. Then, the SUS nut-shaped mold filled with the radical polymerizable raw material composition and the 5mm SUS rod as the pressure-sensitive shaft were installed on the Sun rheometer CR-150 (made by Sunshine Science Co., Ltd.). Then, at a temperature of 23°C, the pressure-sensitive shaft was compressed into the radical polymerizable raw material composition at a speed of 120mm / min until its depth reached 2mm. Then, the maximum load [Kg] at this time was measured. As a result, the maximum load was 6.0Kg.

[0277] In addition, when the maximum load is below 10Kg, the radical polymerizable raw material composition can be injected into the mold frame for mold forming. Therefore, when the maximum load is below 10Kg, it is judged that the operability is good, and when it exceeds 10Kg, it is judged that the operability is poor.

[0278] (3-3) Evaluation of phase morphology

[0279] The phase morphology of the radical polymerizable raw material composition is determined based on the maximum load measured to evaluate operability. Here, when the maximum load is 10Kg or less, the radical polymerizable raw material composition has sufficient fluidity to easily inject the radical polymerizable raw material composition into the mold frame without gaps for mold forming, so the phase morphology of the radical polymerizable raw material composition is determined to be a paste. On the other hand, when the maximum load exceeds 10Kg, the radical polymerizable raw material composition obviously loses fluidity to the extent that the radical polymerizable raw material composition cannot be injected into the mold frame without gaps for mold forming, so the phase morphology of the radical polymerizable raw material composition is determined to be actually solid. As a result, it was confirmed that the maximum load of the obtained radical polymerizable raw material composition was 6.0Kg and it was in a paste state.

[0280] (4) Radical polymerization process (hardening process)

[0281] By injecting the obtained free radical polymerizable raw material composition into a mold frame (length 12㎜×width 18㎜×height 14㎜), free radical polymerization was carried out for 15 hours at a temperature of 120°C and under nitrogen pressure conditions (0.35MPa), thereby obtaining a polyurethane composite material in which fillers are dispersed in a polyurethane resin matrix. In addition, regarding the obtained free radical polymerizable raw material composition, it was confirmed that: from shortly after modulation to a few hours before the start of mold forming and free radical polymerization, no particular increase in viscosity or change in liquid properties was observed, and it was a stable composition at room temperature. In addition, the hardened body obtained by hardening based on free radical polymerization does not have a partially insufficiently hardened part, and a uniform hardened body is obtained.

[0282] In addition, after the free radical polymerizable raw material composition prepared in the same manner was stored at room temperature (25°C) for six months and the phase morphology was evaluated again, it was confirmed that the paste-like properties were maintained unchanged. It can be seen from this that the obtained free radical polymerizable raw material composition can maintain stable properties for an extremely long time. In addition, the free radical polymerizable raw material compositions used in other examples shown in Tables 1 and 2 were also evaluated in the same manner, and it was confirmed that the free radical polymerizable raw material compositions used in all examples can maintain stable properties for an extremely long time.

[0283] (5) Evaluation of polyurethane composite materials (hardened products)

[0284] The obtained polyurethane composite material was evaluated for flexural strength, underwater flexural strength, maintenance rate (water resistance), and uniformity. The evaluation methods and results are shown below.

[0285] [Bending Strength BS d ]

[0286] After the obtained polyurethane composite material (hardened body) was cut out using a low-speed diamond cutter (produced by Buehler), it was ground using #2000 water-resistant sandpaper to produce 10 prismatic test pieces (thickness: about 1.2㎜×width: about 4.0㎜×length: 14.0㎜). Next, a three-point bending test was performed on each test piece using an automatic plotter (produced by Shimadzu Corporation), and the bending load at the maximum point was measured. Then, the flexural strength BS was calculated according to the following formula (6). After setting the distance between the fulcrums to 12.0㎜ and the crosshead speed to 1.0㎜ / min, the bending load at the maximum point was measured. As a result, the average value of the flexural strength BS of the 10 test pieces (flexural strength BS d ) is 337MPa.

[0287] Formula (6) BS = 3PS / 2WB 2

[0288] In formula (6), BS represents the bending strength (MPa), P represents the bending load at the maximum point (N), S represents the distance between the support points (12.0 mm), W represents the width of the test piece (measured value, mm), and B represents the thickness of the test piece (measured value, mm).

[0289] [Bending strength in water BS W ]

[0290] Ten test pieces were manufactured in the same manner as described in the [Bending Strength] column, and all the test pieces were stored in ion exchange water at 37°C for one week. Then, for the test pieces taken out of the ion exchange water, after removing the moisture attached to the surface, a three-point bending test was performed under the same test conditions as described in the [Bending Strength] column, and the bending load at the maximum point of the test pieces after storage in water was measured. Then, for each test piece after storage in water, the bending strength BS was calculated according to formula (6). The result is that the average value of the bending strength BS of the 10 test pieces after storage in water (bending strength BS in water) is W ) is 283MPa.

[0291] [Maintenance rate (water resistance)]

[0292] The maintenance rate, which is an index indicating the water resistance of the hardened body, was calculated according to the following formula (7): In this example, the maintenance rate was 84%, and it was confirmed that the hardened body had high water resistance.

[0293] Formula (7) Maintenance rate (%) = 100 × BS W / BS d

[0294] In formula (7), BS W The average value (MPa) of the flexural strength BS of 10 test pieces stored in water is shown in BS. d The average value (MPa) of the flexural strength BS of 10 test pieces is shown.

[0295] [Uniformity]

[0296] The uniformity of the hardened body was evaluated by visually observing the appearance of the hardened body obtained and the cross-section obtained by roughly dividing the hardened body into two equal parts. Here, whether the hardened body has uniformity is judged based on whether there is hardening unevenness or cracks on the surface and cross-section of the hardened body. When neither hardening unevenness nor cracks are confirmed, it is judged to be uniform, and when at least one of hardening unevenness and cracks is confirmed, it is judged to be uneven. For the hardened body of Example A1, neither hardening unevenness nor cracks were confirmed, which shows that it is uniform.

[0297] (Comparative Example A1)

[0298] A primary raw material composition was prepared in the same manner as in Example A1. The same amount of diisocyanate compound (a2) [XDI] as in Example A1 was added to a self-rotating revolution agitator containing the entire amount of the obtained primary raw material composition and mixed to obtain a raw material composition. In addition, the raw material composition is a composition having the same composition as the addition-polymerization-reactive raw material composition prepared in Example A1, and in the manufacturing process of the polyurethane composite material of Comparative Example A1, it is equivalent to a composition having both the functions of the addition-polymerization-reactive raw material composition used in Example A1 and the functions of the free radical polymerizable raw material composition.

[0299] Next, the obtained composition was immediately injected into a mold frame (length 12mm × width 18mm × height 14mm), and the addition polymerization and free radical polymerization were carried out simultaneously and in parallel for 15 hours at a temperature of 120°C and under nitrogen pressure conditions (0.35MPa), thereby obtaining a polyurethane composite material. After confirming the uniformity of the obtained polyurethane composite material (hardened body), it was found that cracks existed, and it was an uneven hardened body. Therefore, the evaluation of flexural strength, flexural strength in water, and maintenance rate (water resistance) was not performed.

[0300] (Examples A2 to A13)

[0301] A radical polymerizable raw material composition was prepared in the same manner as in Example A1 except that the raw materials, a2 / a1 molar ratio, polymerizable monomer mixing ratio Rr, and filling rate used in Example A1 were changed to those shown in Table 1. The obtained radical polymerizable raw material composition was evaluated in the same manner as in Example A1. The results are shown in Table 2.

[0302] In addition, similarly to Example A1, the obtained free radical polymerizable raw material composition was injected into a mold frame and then subjected to a free radical polymerization step to produce a polyurethane composite material. The obtained polyurethane composite material was evaluated similarly to Example A1. The results are shown in Table 2.

[0303] (Comparative Examples A2 to A5) <Examples containing no non-addition polymerizable radical polymerizable monomer (B) or where the polymerizable monomer mixing ratio Rr is outside the range of 20 wt % to 80 wt %>

[0304] A radical polymerizable raw material composition was prepared in the same manner as in Example A1 except that the raw materials used, the a2 / a1 molar ratio, the polymerizable monomer mixing ratio Rr, and the filling rate were changed to those shown in Table 1. The obtained radical polymerizable raw material composition was evaluated in the same manner as in Example A1. The results are shown in Table 2.

[0305] In addition, similarly to Example A1, the obtained free radical polymerizable raw material composition was injected into a mold frame and then subjected to a free radical polymerization step to produce a polyurethane composite material. The obtained polyurethane composite material was evaluated similarly to Example A1. The results are shown in Table 2.

[0306] [Table 1]

[0307]

[0308] [Table 2]

[0309]

[0310] As shown in Table 2, it can be confirmed that the polyurethane composite materials produced in Examples A1 to A13 are good in strength (flexural strength), water resistance, and uniformity. In addition, the free radical polymerizable pigment composition is also easy to handle, and even if the filling rate is as high as 60% to 85%, the curing is uniform and sufficient.

[0311] On the other hand, in Comparative Example A1 in which addition polymerization and radical polymerization were carried out simultaneously, a uniform hardened body was not obtained. In addition, in Comparative Example A2 which did not contain a non-addition-polymerizable free radical polymerizable monomer (B), and in Comparative Example A3 which contained a non-addition-polymerizable free radical polymerizable monomer (B) but had a polymerizable monomer mixing ratio Rr of less than 20 wt%, the phase morphology was evaluated as solid, and a uniform hardened body was not obtained. Furthermore, the flexural strength and the flexural strength in water were also low values. In addition, in Comparative Example A4 which did not contain a non-addition-polymerizable free radical polymerizable monomer (B) but excessively used a radical polymerizable diol compound (a1) (compared to the stoichiometric ratio), the phase morphology was evaluated as a paste, but the flexural strength in water was a low value. In addition, in Comparative Example A5 in which a non-addition-polymerizable free radical polymerizable monomer (B) was mixed in a manner in which the polymerizable monomer mixing ratio Rr exceeded 80 wt%, the flexural strength in water was a low value.

[0312] 3. Polyurethane composite materials

[0313] Hereinafter, examples and comparative examples of the polyurethane composite material of the first present invention and the polyurethane composite material of the second present invention will be shown together.

[0314] (Example B1)

[0315] The same process as in Example A2 was implemented to manufacture a hardened body (polyurethane composite material). In addition, by carrying out FT-IR measurement on the obtained hardened body and the free radical polymerizable raw material composition used in the manufacture of the hardened body, the free radical polymerizable base residual rate (%) shown in the formula (3) was obtained. In addition, after calculating the initial double bond amount according to the formula (5), the double bond amount (mmol / g) of the hardened body was obtained according to the formula (4). Further, the hardened body was evaluated for initial adhesive strength, durable adhesive strength, flexural strength, flexural strength in water and uniformity. The results are shown in Table 3-4.

[0316] In addition, the FT-IR measurement of the hardened body and the radical polymerizable raw material composition, and the evaluation methods of the initial adhesive strength and the durable adhesive strength are as follows.

[0317] [FT-IR measurement of hardened body and radical polymerizable raw material composition]

[0318] The FT-IR measurement of the obtained hardened body and the radical polymerizable raw material composition used in the production of the hardened body was carried out by the transmission method using a Fourier transform infrared spectrophotometer (Spectrum One, manufactured by Perkin Elmer). The FT-IR measurement of the radical polymerizable raw material composition was carried out by using a disk mold (diameter 15 mm×thickness 1 mm) filled with the radical polymerizable raw material composition as a measurement sample; the FT-IR measurement of the hardened body was carried out by using a disk mold filled with the radical polymerizable raw material composition after being hardened under the same radical polymerization conditions as when the hardened body was produced as a measurement sample. Then, for each measurement sample, two peak areas required for the calculation of the residual rate (%) of the radical polymerizable group represented by formula (3) were measured, namely, the peak area of ​​the absorption peak of the carbonyl group derived from the carbamate bond (ν4920) and the peak area of ​​the absorption peak of the carbon-carbon double bond derived from the radical polymerizable group (ν6170).

[0319] [Evaluation of initial adhesive strength]

[0320] The obtained hardened body was cut out with a low-speed diamond cutter (Buehler), and then ground with #1500 water-resistant sandpaper to obtain a test piece (length 12mm × width 14mm × height 3mm). Then, the surface of the test piece was treated with alumina sandblasting, ultrasonically cleaned with ion exchange water, and then dried by spraying dry air. Then, a double-sided tape with holes of 3mm was pasted on the surface of the test piece, and the surface exposed from the hole was used as the adhesive surface. After ESTECEMII (Tokuyama Dental Co., Ltd.) was applied to the adhesive surface, a cylindrical SUS accessory (diameter 8mm, length 25mm) was bonded to the adhesive surface to obtain a joint body. The obtained bonded body was left to stand for 1 hour under a humid condition of 37°C, and then immersed in water at 37°C for 24 hours to obtain a test piece with accessories (measurement sample for initial adhesion strength evaluation). The tensile test was performed using a universal testing machine (automatic plotter; manufactured by Shimadzu Corporation) at a crosshead speed of 2 mm / min. At this time, the average value of the tensile adhesion strength measured for the five measurement samples was taken as the initial adhesion strength.

[0321] [Durable Adhesion Strength Evaluation]

[0322] After placing the test piece with accessories manufactured in the same manner as described in the [Evaluation of Initial Adhesion Strength] column into a heat shock tester, the following operation was repeated 3000 times, thereby obtaining a test piece with accessories after the heat shock test (measurement sample for evaluation of durable adhesion strength), wherein the operation refers to the operation of immersing in a 5°C water tank for 30 seconds, moving to a 55°C water tank for 30 seconds, and returning to a 5°C water tank again. Next, the tensile adhesion strength was measured in the same manner as described in the [Evaluation of Initial Adhesion Strength] column. At this time, the average value of the tensile adhesion strength measured for the five measurement samples was taken as the durable adhesion strength.

[0323] (Example B2)

[0324] The same steps as in Example A8 were carried out to produce a hardened body (polyurethane composite material). Then, the free radical polymerizable group residual rate (%) and double bond amount (mmol / g) were determined in the same manner as in Example B1, and the initial adhesive strength and the durable adhesive strength were evaluated. The results are shown in Table 3-4.

[0325] (Example B3)

[0326] The same steps as in Example A10 were carried out to produce a hardened body (polyurethane composite material). Then, the free radical polymerizable group residual rate (%) and double bond amount (mmol / g) were determined in the same manner as in Example B1, and the initial adhesive strength and the durable adhesive strength were evaluated. The results are shown in Table 3-4.

[0327] (Comparative Example B1)

[0328] First, add 19 parts by mass of UDMA, 6 parts by mass of 3G, and 0.1 parts by mass of BPO, and stir with an electromagnetic stirrer. Then, add 53 parts by mass of F1 and 22 parts by mass of F2, and mix them evenly with a self-rotating and revolving stirrer (manufactured by KURABO Corporation), thereby obtaining a raw material composition. After the obtained raw material composition is injected into a mold frame (length 12 mm × width 18 mm × height 14 mm), the temperature is raised to 90°C under nitrogen pressure conditions (0.3 MPa), and free radical polymerization is carried out for 15 hours. Then, the hardened body formed in the mold frame is taken out from the mold frame. Then, in the same manner as in Example B1, the residual rate (%) of free radical polymerizable groups and the amount of double bonds (mmol / g) are determined, and the initial adhesion strength and durable adhesion strength are evaluated. The results are shown in Table 3-4.

[0329] [Table 3]

[0330]

[0331] ※1: Rr=100×Br / [a1r+a2r+Ar+Br]

[0332] ※2: C: 10-hour half-life temperature of the radical polymerization initiator (℃) - heating temperature during radical polymerization (℃)

[0333] ※3: Refer to the description of Comparative Example B1 in the manual

[0334] [Table 4]

[0335]

[0336] ※1: Adhesion durability = 100 × durable adhesion strength (MPa) / initial adhesion strength (MPa)

[0337] ※2:Maintenance rate = 100 × BSw (MPa) / BSd (MPa)

[0338] As shown in Table 3-4, in Examples B1 to B3, it was confirmed that both the initial adhesive strength and the durable adhesive strength were high due to the large amount of double bonds, and the adhesive durability, which is the ratio of the durable adhesive strength to the initial adhesive strength, was as high as 77.6% to 81.8%. On the other hand, in Comparative Example B1 with a small amount of double bonds, the initial adhesive strength (14.5 MPa) was low.

[0339] 4. Polyurethane resin matrix of polyurethane composite materials

[0340] Experimental examples of resin materials corresponding to the polyurethane resin matrix constituting the polyurethane composite material of the first and second polyurethane composite materials of the present invention are shown below.

[0341] In addition, in the following description, Experimental Example A is an experimental example related to the resin material equivalent to the polyurethane resin matrix constituting the polyurethane composite material of the first present invention and the polyurethane composite material of the second present invention, and Experimental Example B is an experimental example related to the resin material not equivalent to the polyurethane resin matrix constituting the polyurethane composite material of the first present invention and the second polyurethane composite material of the present invention.

[0342] (Experimental Example A1)

[0343] A hardened body was produced in the same manner as in Example A2 except that filler (D) was not mixed when preparing the free radical polymerizable raw material composition (please refer to Table 5 for details of the production conditions). Next, for the obtained hardened body, the free radical polymerizable group residual rate and double bond amount were obtained in the same manner as in Example B1 corresponding to Example A2, and the initial adhesive strength and the durable adhesive strength were evaluated. The results are shown in Table 6.

[0344] (Experimental Example A2)

[0345] A hardened body was produced in the same manner as in Example A10 except that filler (D) was not mixed when preparing the free radical polymerizable raw material composition (please refer to Table 5 for details of the production conditions). Next, for the obtained hardened body, the free radical polymerizable group residual rate and double bond content were determined in the same manner as in Example B3 corresponding to Example A10, and the initial adhesive strength and durable adhesive strength were evaluated. The results are shown in Table 6.

[0346] (Experimental Examples A3 to A7 and Experimental Examples B1 to B4)

[0347] From the comparison results of Examples B1 and B3 shown in Tables 3-4 and Experimental Examples A1 and A2 shown in Tables 5-6, it is clear that the presence or absence of mixed filler (D) has almost no effect on the double bond amount and adhesion durability. Therefore, it is clear that the difference in the polyurethane resin matrix is ​​also directly reflected in the physical properties such as the strength of the polyurethane composite material including the polyurethane resin matrix and the filler dispersed in the polyurethane resin matrix.

[0348] Therefore, for Experimental Examples A3 to A7 and Experimental Examples B1 to B3, the resin material corresponding to the polyurethane resin matrix was manufactured and various evaluations were performed in the same manner as in Experimental Examples A1 and A2. In addition, the resin materials of Experimental Examples A3 to A7 and Experimental Examples B1 to B3 were manufactured by the method for manufacturing the polyurethane composite material of the present invention under the conditions shown in Table 5, except that the filler (D) was not used. In addition, in Experimental Examples A3 to A7 and Experimental Examples B1 to B4, the other manufacturing conditions not described in Table 5 were in accordance with the conditions of Example A1.

[0349] In Experimental Example B4, a resin material was produced by radical polymerization in the same manner as in Example A1 except that a radical polymerizable raw material composition containing only a (meth)acrylic acid polymerizable monomer and a radical polymerization initiator was used as a starting material as shown in Table 5, and various evaluations were performed on the resin material in the same manner as in Experimental Examples A1 and A2. The results are shown in Table 6.

[0350] [Table 5]

[0351]

[0352] [Table 6]

[0353]

[0354] ※1: Adhesion durability = 100 × durable adhesion strength (MPa) / initial adhesion strength (MPa)

[0355] As shown in Table 6, it was confirmed that the residual rate of free radical polymerizable groups and the amount of double bonds in Experimental Examples A1 and A2 were equal to or approximately equal to the values ​​in Examples B1 and B3, respectively. In addition, since Experimental Examples A1 and A2 did not contain fillers, the absolute values ​​of initial adhesion strength and durable adhesion strength tended to be slightly lower than the values ​​in Examples B1 and B3 (about 20% for initial adhesion strength and about 12% for durable adhesion strength, which were lower values), but both showed good values, and further, the characteristics of high adhesion durability were maintained.

[0356] In addition, in Experimental Examples A1 to A7, the double bond amount was in the range of 0.51 mmol / g to 0.91 mmol / g, and both the initial adhesive strength and the adhesive durability showed relatively high values. In contrast, in Experimental Examples B1 and B2, in which a non-radical polymerizable diol compound was used instead of the radical polymerizable diol compound (a1), the double bond amount was relatively small, 0.20 mmol / g to 0.37 mmol / g, due to the small number of radical polymerizable groups and the fact that the polyurethane component and the non-addition polymerizable radical polymerizable monomer (B) were not copolymerized. As a result, in Experimental Examples B1 and B2, the initial adhesive strength was 13.8 MPa to 14.1 MPa, which was lower than that of Experimental Examples A1 to A7, and the adhesive durability was 36.9% to 46.4%, which was very low compared to Experimental Examples A1 to A7. In Experiment B3, in which the ratio of the radical polymerizable diol compound (a1) to the diisocyanate compound (a2) was small, the double bond amount was small, 0.31 mmol / g, and the adhesion durability was 76.5%, but the initial adhesion strength was a low value of 14.9 MPa. In Experiment B4, in which the obtained resin material was (meth) acrylic acid, the initial adhesion strength was a low value of 12.7 MPa.

Claims

1. A method for producing a polyurethane composite material, characterized in that: include: A polyaddition reaction step, in a polyaddition reaction raw material composition comprising a diol compound (a1) having one or more free radical polymerizable groups, a diisocyanate compound (a2), and a polymerizable monomer (B), by causing the diol compound (a1) and the diisocyanate compound (a2) to undergo a polyaddition reaction to form a polyurethane component (A) having a number average molecular weight of 1500 to 5000 and having a free radical polymerizable group, wherein the polymerizable monomer (B) comprises at least one selected from the group consisting of a polymerizable monomer represented by the following structural formula (1), EO-modified trimethylolpropane triacrylate, and ethylene glycol diacrylate, and does not contain a hydroxyl group, an amino group, a carboxyl group, an isocyanate group, and a mercapto group in the molecule, a radical polymerizable raw material composition preparation step of preparing a radical polymerizable raw material composition comprising the polyurethane component (A), the polymerizable monomer (B), a radical polymerization initiator (C) and a filler (D); A free radical polymerization step, after completing the addition polymerization step and the free radical polymerizable raw material composition preparation step, by using the free radical polymerizable raw material composition to perform free radical polymerization to form a polyurethane composite material; The mixing ratio Rr of the polymerizable monomer represented by the following formula (1) is 20 wt% to 80 wt%, [Chemical formula 1] In the structural formula (1), R 11 and R 12 is a hydrogen atom or a methyl group, n1 is an integer from 1 to 10, Formula (1) Rr=100×Br / [a1r+a2r+Ar+Br] In the formula (1), a1r represents the mass part of the unreacted diol compound (a1) remaining in the free radical polymerizable raw material composition, a2r represents the mass part of the unreacted diisocyanate compound (a2) remaining in the free radical polymerizable raw material composition, Ar represents the mass part of the polyurethane component (A) contained in the free radical polymerizable raw material composition, and Br represents the mass part of the polymerizable monomer (B) contained in the free radical polymerizable raw material composition.

2. The method for producing a polyurethane composite material according to claim 1, characterized in that: The content ratio of the filler (D) in the radical polymerizable raw material composition is 60 wt % to 85 wt %.

3. The method for producing a polyurethane composite material according to claim 1 or 2, characterized in that: As the radical polymerization initiator (C), a thermal radical polymerization initiator is used. The radical polymerization step is performed in a state where the material is heated to a temperature of -10°C to +25°C, which is the 10-hour half-life temperature of the thermal radical polymerization initiator.

4. The method for producing a polyurethane composite material according to claim 1 or 2, characterized in that: The polyaddition reactive raw material composition is prepared by preparing a primary raw material composition containing the diol compound (a1), the polymerizable monomer (B) and the filler (D), and then further adding the diisocyanate compound (a2) to the primary raw material composition.

5. The method for producing a polyurethane composite material according to claim 1 or 2, characterized in that: The radical polymerizable raw material composition is a paste-like composition.

6. The method for producing a polyurethane composite material according to claim 5, characterized in that: The radical polymerization step is performed after the radical polymerizable raw material composition is injected into the mold frame.

7. A polyurethane composite material, characterized in that: The product is produced through a polyaddition reaction step, a radical polymerizable raw material composition preparation step, and a radical polymerization step. in, In the polyaddition reaction step, in a polyaddition reaction raw material composition comprising a diol compound (a1) having one or more free radical polymerizable groups, a diisocyanate compound (a2), and a polymerizable monomer (B), the diol compound (a1) and the diisocyanate compound (a2) are subjected to a polyaddition reaction to form a polyurethane component (A) having a number average molecular weight of 1500 to 5000 and having a free radical polymerizable group, wherein the polymerizable monomer (B) comprises at least one selected from the group consisting of a polymerizable monomer represented by the following structural formula (1), EO-modified trimethylolpropane triacrylate, and ethylene glycol diacrylate, and does not contain a hydroxyl group, an amino group, a carboxyl group, an isocyanate group, and a mercapto group in the molecule. In the radical polymerizable raw material composition preparation step, a radical polymerizable raw material composition comprising the polyurethane component (A), the polymerizable monomer (B), a radical polymerization initiator (C) and a filler (D) is prepared. In the radical polymerization step, after the addition polymerization step and the radical polymerizable raw material composition preparation step are completed, free radical polymerization is performed using the radical polymerizable raw material composition to form a polyurethane composite material; The mixing ratio Rr of the polymerizable monomer represented by the following formula (1) is 20 wt% to 80 wt%, The content ratio of the filler (D) in the radical polymerizable raw material composition is 60 wt % to 85 wt %. As the radical polymerization initiator (C), a thermal radical polymerization initiator is used. The radical polymerization step is carried out in a state where the material is heated to a temperature of -10°C to +25°C, which is the 10-hour half-life temperature of the thermal radical polymerization initiator. In the copolymer of the polyurethane component (A) and the polymerizable monomer (B) formed in the radical polymerization step, 10% to 25% of the total amount of radical polymerizable groups possessed by the diol compound (a1) and the polymerizable monomer (B) contained in the radical polymerizable raw material composition remains; [Chemical formula 2] In the structural formula (1), R 11 and R 12 is a hydrogen atom or a methyl group, n1 is an integer from 1 to 10, Formula (1) Rr=100×Br / [a1r+a2r+Ar+Br] In the formula (1), a1r represents the mass part of the unreacted diol compound (a1) remaining in the free radical polymerizable raw material composition, a2r represents the mass part of the unreacted diisocyanate compound (a2) remaining in the free radical polymerizable raw material composition, Ar represents the mass part of the polyurethane component (A) contained in the free radical polymerizable raw material composition, and Br represents the mass part of the polymerizable monomer (B) contained in the free radical polymerizable raw material composition.

8. A polyurethane composite material, characterized in that: The polyurethane composite material is composed of a composite material including a polyurethane resin matrix and a filler dispersed in the polyurethane resin matrix. The polyurethane resin matrix is ​​composed of a copolymer of a polyurethane having a number average molecular weight of 1500 to 5000 and having a free radical polymerizable group and a free radical polymerizable monomer, wherein the free radical polymerizable monomer comprises at least one selected from the group consisting of a polymerizable monomer represented by the following structural formula (1), EO-modified trimethylolpropane triacrylate and dioxane glycol diacrylate, and does not contain a hydroxyl group, an amino group, a carboxyl group, an isocyanate group and a mercapto group in the molecule. The content of free radical polymerizable carbon-carbon double bonds contained in 1 g of the polyurethane resin matrix is ​​0.5 mmol / g to 1.0 mmol / g, The content of the filler in the composite material is 60wt% to 85wt%. [Chemical formula 3] In the structural formula (1), R 11 and R 12 is a hydrogen atom or a methyl group, and n1 is an integer of 1 to 10.

9. A dental cutting material, characterized in that: The dental cutting material is composed of a polyurethane composite material. The polyurethane composite material is manufactured through a polyaddition reaction step, a free radical polymerizable raw material composition preparation step, and a free radical polymerization step. in, In the polyaddition reaction step, in a polyaddition reaction raw material composition comprising a diol compound (a1) having one or more free radical polymerizable groups, a diisocyanate compound (a2), and a polymerizable monomer (B), the diol compound (a1) and the diisocyanate compound (a2) are subjected to a polyaddition reaction to form a polyurethane component (A) having a number average molecular weight of 1500 to 5000 and having a free radical polymerizable group, wherein the polymerizable monomer (B) comprises at least one selected from the group consisting of a polymerizable monomer represented by the following structural formula (1), EO-modified trimethylolpropane triacrylate, and ethylene glycol diacrylate, and does not contain a hydroxyl group, an amino group, a carboxyl group, an isocyanate group, and a mercapto group in the molecule. In the radical polymerizable raw material composition preparation step, a radical polymerizable raw material composition comprising the polyurethane component (A), the polymerizable monomer (B), a radical polymerization initiator (C) and a filler (D) is prepared. In the radical polymerization step, after the addition polymerization step and the radical polymerizable raw material composition preparation step are completed, free radical polymerization is performed using the radical polymerizable raw material composition to form a polyurethane composite material; The mixing ratio Rr of the polymerizable monomer represented by the following formula (1) is 20 wt% to 80 wt%, The content ratio of the filler (D) in the radical polymerizable raw material composition is 60 wt % to 85 wt %. As the radical polymerization initiator (C), a thermal radical polymerization initiator is used. The radical polymerization step is carried out in a state where the material is heated to a temperature of -10°C to +25°C, which is the 10-hour half-life temperature of the thermal radical polymerization initiator. In the copolymer of the polyurethane component (A) and the polymerizable monomer (B) formed in the radical polymerization step, 10% to 25% of the total amount of radical polymerizable groups possessed by the diol compound (a1) and the polymerizable monomer (B) contained in the radical polymerizable raw material composition remains; [Chemical formula 4] In the structural formula (1), R 11 and R 12 is a hydrogen atom or a methyl group, n1 is an integer from 1 to 10, Formula (1) Rr=100×Br / [a1r+a2r+Ar+Br] In the formula (1), a1r represents the mass part of the unreacted diol compound (a1) remaining in the free radical polymerizable raw material composition, a2r represents the mass part of the unreacted diisocyanate compound (a2) remaining in the free radical polymerizable raw material composition, Ar represents the mass part of the polyurethane component (A) contained in the free radical polymerizable raw material composition, and Br represents the mass part of the polymerizable monomer (B) contained in the free radical polymerizable raw material composition.

10. A dental cutting material, characterized in that: The dental cutting material is composed of a polyurethane composite material. The polyurethane composite material is composed of a composite material including a polyurethane resin matrix and a filler dispersed in the polyurethane resin matrix. The polyurethane resin matrix is ​​composed of a copolymer of a polyurethane having a number average molecular weight of 1500 to 5000 and having a free radical polymerizable group and a free radical polymerizable monomer, wherein the free radical polymerizable monomer comprises at least one selected from the group consisting of a polymerizable monomer represented by the following structural formula (1), EO-modified trimethylolpropane triacrylate and dioxane glycol diacrylate, and does not contain a hydroxyl group, an amino group, a carboxyl group, an isocyanate group and a mercapto group in the molecule. The content of free radical polymerizable carbon-carbon double bonds contained in 1 g of the polyurethane resin matrix is ​​0.5 mmol / g to 1.0 mmol / g, The content of the filler in the composite material is 60wt% to 85wt%. [Chemical formula 5] In the structural formula (1), R 11 and R 12 is a hydrogen atom or a methyl group, and n1 is an integer of 1 to 10.

Citation Information

Patent Citations

  • MOLDED PRODUCT FROM POLYURETHANE MATERIAL, AND PRODUCTION METHOD AND USE THEREOF

    JP2002527588A

  • Polyurethane-based dental restoration material

    JP2019210233A

  • Process for producing dentures of denture parts and storable dental materials suitable for this

    US4787850A

  • Radically polymerizable resin composition, molding material, and molded article

    CN103974986A

  • Polymerizable monomer composition for dental material

    CN106132383A